Polarizing plate, polarizing plate with retardation layer, and image display device including said polarizing plate or said polarizing plate with retardation layer

The polarizer with a protective layer, optimized for birefringence and orientation, addresses the issue of cracking in thin, non-rectangular polarizing plates, ensuring both thinness and optical quality for image display devices.

JP7654670B2Active Publication Date: 2025-04-01NITTO DENKO CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2022540177
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-06
Filing Date
2021-07-16
Publication Date
2025-04-01
Estimated Expiration
2041-07-16

AI Technical Summary

Technical Problem

Conventional thin polarizers are prone to cracking in irregularly shaped processing sections, which is a challenge in the development of thinner, non-rectangular polarizing plates for image display devices.

Method used

A polarizer with a protective layer made of a resin film with a thickness of 10 μm or less, composed of a polyvinyl alcohol-based resin film containing a dichroic material, and optimized with specific birefringence, in-plane phase difference, and orientation function values to prevent cracking in non-rectangular shapes.

Benefits of technology

The proposed polarizer solution achieves a thin, crack-resistant design that maintains acceptable optical properties, making it suitable for use in thin, irregularly shaped image display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654670000004
    Figure 0007654670000004
  • Figure 0007654670000005
    Figure 0007654670000005
  • Figure 0007654670000006
    Figure 0007654670000006
Patent Text Reader

Abstract

Provided is a polarizing plate in which the occurrence of cracking in a deformed portion is suppressed although being extremely thin. This polarizing plate includes a polarizer, and a protective layer provided on at least one side of the polarizer, and has a deformed shape other than a rectangular shape. The protective layer comprises a resin film having a thickness of 10 μm or less. The polarizer comprises a PVA-based resin film containing a dichroic material. In one embodiment, expression (1) is satisfied when the single transmittance of the polarizer is denoted by x%, and the birefringence of PVA-based resin is denoted by y. In another embodiment, expression (2) is satisfied when the single transmittance of the polarizer is denoted by x%, and the in-plane phase difference of the PVA-based resin film is denoted by z nm. In still another embodiment, expression (3) is satisfied when the single transmittance of the polarizer is denoted by x%, and the orientation function of the PVA-based resin is denoted by f. In yet another embodiment, the piercing strength of the polarizer is 30 gf / μm or more. (1): y < -0.011x+0.525 (2): z < -60x+2875 (3): f < -0.018x+1.11
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizing plate, a polarizing plate with a retardation layer, and an image display device including the polarizing plate or the polarizing plate with a retardation layer. [Background technology]

[0002] In recent years, image display devices such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices) have rapidly become widespread. Due to the image formation method of the image display device, a polarizing plate is arranged on at least one side of the image display device. In recent years, as the demand for thinner image display devices has increased, the demand for thinner polarizing plates has also increased. Incidentally, in recent years, there are cases where it is desired to process the polarizing plate into a shape other than a rectangle (irregular shape processing: for example, formation of notches and / or through holes). However, there is a problem that cracks are likely to occur in the irregularly processed parts of the thin polarizing plate. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2001-343521 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made to solve the above-mentioned problems in the conventional art, and a main object of the present invention is to provide a polarizing plate which is extremely thin and yet suppresses the occurrence of cracks in the irregularly shaped portions. [Means for solving the problem]

[0005] A polarizing plate according to one embodiment of the present invention has a polarizer and a protective layer disposed on at least one side of the polarizer, and has an irregular shape other than a rectangle. The protective layer is made of a resin film having a thickness of 10 μm or less. The polarizer is made of a polyvinyl alcohol-based resin film containing a dichroic material, and satisfies the following formula (1) when the single transmittance is x% and the birefringence of the polyvinyl alcohol-based resin is y: y<-0.011x+0.525 (1). A polarizing plate according to another embodiment of the present invention has a polarizer and a protective layer disposed on at least one side of the polarizer, and has an irregular shape other than a rectangle. The protective layer is made of a resin film having a thickness of 10 μm or less. The polarizer is made of a polyvinyl alcohol-based resin film containing a dichroic material, and satisfies the following formula (2) when the single transmittance is x% and the in-plane retardation of the polyvinyl alcohol-based resin film is z nm: z<-60x+2875 (2). A polarizing plate according to yet another embodiment of the present invention has a polarizer and a protective layer disposed on at least one side of the polarizer, and has an irregular shape other than a rectangle. The protective layer is made of a resin film having a thickness of 10 μm or less. The polarizer is made of a polyvinyl alcohol-based resin film containing a dichroic material, and satisfies the following formula (3) when the single transmittance is x% and the orientation function of the polyvinyl alcohol-based resin is f: f<-0.018x+1.11 (3). A polarizing plate according to yet another embodiment of the present invention includes a polarizer and a protective layer disposed on at least one side of the polarizer, and has an irregular shape other than a rectangle. The protective layer is made of a resin film having a thickness of 10 μm or less. The polarizer is made of a polyvinyl alcohol-based resin film containing a dichroic material, and the piercing strength of the polarizer is 30 gf / μm or more. In one embodiment, the polarizer has a thickness of 10 μm or less. In one embodiment, the polarizer has a single transmittance of 40.0% or more and a polarization degree of 99.0% or more. In one embodiment, the irregular shape is selected from the group consisting of a through hole, a V-notch, a U-notch, a recess that resembles a boat shape when viewed in a plan view, a rectangular recess when viewed in a plan view, an R-shaped recess that resembles a bathtub shape when viewed in a plan view, and combinations thereof. In one embodiment, the U-notch has a radius of curvature of 5 mm or less. In one embodiment, the resin film contains at least one resin selected from an epoxy resin and a (meth)acrylic resin. In one embodiment, the resin film is made of a photocationically cured epoxy resin, and the softening temperature of the resin film is 100° C. or higher. In one embodiment, the resin film is formed from a solidified coating of an organic solvent solution of an epoxy resin, and the softening temperature of the resin film is 100° C. or higher. In one embodiment, the resin film is composed of a solidified coating film of a solution of a thermoplastic (meth)acrylic resin in an organic solvent, and the softening temperature of the resin film is equal to or higher than 100° C. In one embodiment, the thermoplastic (meth)acrylic resin has at least one unit selected from the group consisting of a lactone ring unit, a glutaric anhydride unit, a glutarimide unit, a maleic anhydride unit, and a maleimide unit. According to another aspect of the present invention, there is provided a polarizing plate with a retardation layer, the polarizing plate with a retardation layer comprising the above polarizing plate and a retardation layer, the retardation layer being disposed on the side of the polarizer opposite to the side on which the protective layer is disposed. In one embodiment, the retardation layer has Re(550) of 100 nm to 190 nm, Re(450) / Re(550) is 0.8 or more and less than 1, and the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is 40° to 50°. In one embodiment, the retardation layer is laminated on the polarizing plate via a pressure-sensitive adhesive layer. According to yet another aspect of the present invention, there is provided an image display device, the image display device including the above polarizing plate or the above retardation layer-attached polarizing plate. Effect of the Invention

[0006] According to an embodiment of the present invention, in a polarizing plate having an irregular shape (irregularly processed portion), by controlling the orientation state of the polyvinyl alcohol (PVA) resin of the polarizer, it is possible to realize a polarizing plate that is extremely thin and suppresses the occurrence of cracks in the irregularly processed portion. Moreover, such a polarizer (as a result, a polarizing plate) can exhibit optical properties that are acceptable for practical use. [Brief description of the drawings]

[0007] [Figure 1] 1 is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention. [Diagram 2] 4 is a schematic plan view illustrating an example of an irregular shape or irregularly processed portion in a polarizing plate according to an embodiment of the present invention. FIG. [Diagram 3] 10A to 10C are schematic plan views illustrating modified examples of irregular shapes or irregularly processed portions in a polarizing plate according to an embodiment of the present invention. [Figure 4] 13A to 13C are schematic plan views illustrating further modified examples of the irregular shape or irregularly processed portion in the polarizing plate according to the embodiment of the present invention. [Diagram 5] 13A to 13C are schematic plan views illustrating further modified examples of the irregular shape or irregularly processed portion in the polarizing plate according to the embodiment of the present invention. [Figure 6] FIG. 2 is a schematic diagram showing an example of a drying shrinkage treatment using a heated roll in a method for producing a polarizer that can be used in a polarizing plate according to an embodiment of the present invention. [Figure 7] 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. [Figure 8] 1 is a graph showing the relationship between the single transmittance of the polarizers produced in the examples and comparative examples and the birefringence of the PVA-based resin. [Figure 9] 1 is a graph showing the relationship between the single transmittance of the polarizers produced in the Examples and Comparative Examples and the in-plane retardation of the PVA-based resin films. [Figure 10] 1 is a graph showing the relationship between the single transmittance of the polarizers produced in the examples and comparative examples and the orientation function of the PVA-based resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0009] A. Polarizing plate A-1. Overall structure of polarizing plate FIG. 1 is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention. The polarizing plate 100 in the illustrated example has a polarizer 10 and a protective layer 20 arranged on one side of the polarizer 10. Depending on the purpose, another protective layer (not shown) may be provided on the opposite side of the polarizer 10 to the protective layer 20. The protective layer 20 is composed of a resin film having a thickness of 10 μm or less. The polarizing plate may be used as a viewer-side polarizing plate of an image display device, or may be used as a backside polarizing plate. The polarizing plate is typically used as a viewer-side polarizing plate. In this case, the protective layer 20 may be arranged on the viewer side (opposite the image display cell).

[0010] The polarizing plate according to the embodiment of the present invention has an irregular shape other than a rectangle. In this specification, "having an irregular shape other than a rectangle" means that the planar shape of the polarizing plate is a shape other than a rectangle. The irregular shape is typically an irregularly processed part that has been processed into an irregular shape. Therefore, "a polarizing plate having an irregular shape other than a rectangle" (hereinafter, sometimes referred to as "irregularly shaped polarizing plate") includes not only the case where the entire irregularly shaped polarizing plate (i.e., the outer edge that defines the planar shape of the polarizing plate) is other than rectangular, but also the case where an irregularly shaped part is formed in a part spaced inward from the outer edge of a rectangular polarizing plate. In a polarizing plate, such an irregularly shaped part is likely to cause cracks, but according to the embodiment of the present invention, such cracks can be significantly suppressed. More specifically, it is as follows. In a normal (i.e., non-irregular) polarizing plate (substantially a polarizer), cracks often occur along the absorption axis (stretching direction) of the polarizer. On the other hand, in the irregularly shaped part, an L-shaped crack (a crack in a diagonal direction to the absorption axis) may occur. According to an embodiment of the present invention, as described later, by making the orientation of the molecular chains of the PVA-based resin in the absorption axis direction of the polarizer more gentle than that of conventional polarizers, not only normal cracks but also such L-shaped cracks can be significantly suppressed.

[0011] Examples of the irregular shape (irregularly processed part) include, for example, a corner chamfered in an R shape, a through hole, and a cut part that becomes a recess when viewed from above, as shown in Figs. 2 and 3. Representative examples of the recess include a shape that resembles a boat shape, a rectangle, an R shape that resembles a bathtub shape, a V-shaped notch, and a U-shaped notch. Another example of the irregular shape (irregularly processed part) is a shape that corresponds to the meter panel of an automobile, as shown in Figs. 4 and 5. This shape includes a part whose outer edge is formed in an arc shape along the rotation direction of the meter needle and whose outer edge forms a V-shape (including an R-shape) that is convex inward in the planar direction. Needless to say, the shape of the irregular shape (irregularly processed part) is not limited to the illustrated example. For example, the shape of the through hole may be any appropriate shape (for example, an ellipse, a triangle, a square, a pentagon, a hexagon, or an octagon) depending on the purpose, other than the approximately circular shape shown in the illustrated example. The through hole may be provided at any appropriate position depending on the purpose. The through hole may be provided at the approximate center of the longitudinal end of the rectangular polarizing plate as shown in FIG. 3, at a predetermined position of the longitudinal end, or at a corner of the polarizing plate; it may be provided at the short-side end of the rectangular polarizing plate (not shown); or it may be provided at the center of the irregular polarizing plate as shown in FIG. 4 or FIG. 5. As shown in FIG. 3, a plurality of through holes may be provided. Furthermore, the shapes of the illustrated examples may be appropriately combined according to the purpose. For example, a through hole may be formed at any position of the irregular polarizing plate in FIG. 2; a V-shaped notch and / or a U-shaped notch may be formed at any appropriate position of the outer edge of the irregular polarizing plate in FIG. 4 or FIG. 5. Such an irregular polarizing plate may be suitably used in an image display device such as an automobile meter panel, a smartphone, a tablet PC, or a smart watch. For example, when the irregular shape includes an R shape, the radius of curvature is, for example, 0.2 mm or more, for example, 1 mm or more, or for example, 2 mm or more. On the other hand, the radius of curvature is, for example, 10 mm or less, or for example, 5 mm or less. Furthermore, for example, when the irregular shape is a U-shaped notch, its radius of curvature (the radius of curvature of the U-shaped portion) is, for example, 5 mm or less, for example, 1 mm to 4 mm, or for example, 2 mm to 3 mm.

[0012] The irregular shape (irregularly shaped part) can be formed by any suitable method. Specific examples of the forming method include cutting with an end mill, punching with a punching blade such as a Thomson blade, and cutting by laser light irradiation. These methods may be combined.

[0013] A-2. Polarizer The polarizer is composed of a PVA-based resin film containing a dichroic material. In one embodiment, the polarizer satisfies the following formula (1) when the single transmittance is x% and the birefringence of the polyvinyl alcohol-based resin constituting the polarizer is y. In one embodiment, the polarizer satisfies the following formula (2) when the single transmittance is x% and the in-plane retardation of the polyvinyl alcohol-based resin film constituting the polarizer is z nm. In one embodiment, the polarizer satisfies the following formula (3) when the single transmittance is x% and the orientation function of the polyvinyl alcohol-based resin constituting the polarizer is f. In one embodiment, the piercing strength of the polarizer is 30 gf / μm or more. y<-0.011x+0.525 (1) z<-60x+2875 (2) f<-0.018x+1.11 (3)

[0014] The birefringence of the PVA-based resin in the polarizer (hereinafter referred to as the birefringence of PVA or Δn of PVA), the in-plane retardation of the PVA-based resin film (hereinafter referred to as the "in-plane retardation of PVA"), the orientation function of the PVA-based resin (hereinafter referred to as the "orientation function of PVA"), and the piercing strength of the polarizer are all values ​​related to the degree of orientation of the molecular chain of the PVA-based resin constituting the polarizer. Specifically, the birefringence, in-plane retardation, and orientation function of PVA can become large with an increase in the degree of orientation, and the piercing strength can decrease with an increase in the degree of orientation. The polarizer according to the embodiment of the present invention (i.e., a polarizer satisfying the above formulas (1) to (3) or the piercing strength) is suppressed from thermally shrinking in the absorption axis direction because the orientation of the molecular chain of the PVA-based resin in the absorption axis direction is gentler than that of conventional polarizers. As a result, such a polarizer (as a result, a polarizing plate) can suppress the occurrence of cracks in the irregularly processed part while being extremely thin. In addition, such a polarizer (and thus a polarizing plate) is also excellent in flexibility and bending durability, and therefore can be preferably applied to a curved image display device, more preferably a bendable image display device, and even more preferably a foldable image display device. Conventionally, it has been difficult to obtain acceptable optical properties (typically, single transmittance and degree of polarization) with a polarizer having a low degree of orientation, but the polarizer used in the embodiment of the present invention can achieve both a lower degree of orientation of the PVA-based resin than conventional ones and acceptable optical properties.

[0015] The polarizer preferably satisfies the following formula (1a) and / or formula (2a), and more preferably satisfies the following formula (1b) and / or formula (2b). -0.004x+0.18 <y<-0.011x+0.525 (1a) -0.003x+0.145 <y<-0.011x+0.520 (1b) -40x+1800 <z<-60x+2875 (2a) -30x+1450 <z<-60x+2850 (2b)

[0016] In this specification, the in-plane retardation of the PVA is the in-plane retardation value of the PVA-based resin film at 23°C and a wavelength of 1000 nm. By using the near-infrared region as the measurement wavelength, it is possible to eliminate the influence of iodine absorption in the polarizer and to measure the retardation. In addition, the birefringence (in-plane birefringence) of the PVA is the value obtained by dividing the in-plane retardation of the PVA by the thickness of the polarizer.

[0017] The in-plane retardation of PVA is evaluated as follows: First, the retardation value is measured at multiple wavelengths of 850 nm or more, and the measured retardation value: R(λ) is plotted against the wavelength: λ, and this is fitted to the Sellmeier equation below by the least squares method. Here, A and B are fitting parameters and are coefficients determined by the least squares method. R(λ)=A+B / (λ 2 -600 2 ) In this case, the retardation value R(λ) can be separated into an in-plane retardation value (Rpva) of PVA that has no wavelength dependency and an in-plane retardation value (Ri) of iodine that has strong wavelength dependency, as shown below. Rpva= A Ri = B / (λ 2 -600 2 ) Based on this separation formula, the in-plane retardation (i.e., Rpva) of PVA at a wavelength λ=1000 nm can be calculated. The method for evaluating the in-plane retardation of PVA is also described in Japanese Patent No. 5932760, and can be referred to as necessary. In addition, the birefringence (Δn) of the PVA can be calculated by dividing this retardation by the thickness.

[0018] Commercially available devices for measuring the in-plane retardation of PVA at a wavelength of 1000 nm include the KOBRA-WR / IR series and KOBRA-31X / IR series manufactured by Oji Measurement Co., Ltd.

[0019] The orientation function (f) of the polarizer preferably satisfies the following formula (3a), and more preferably satisfies the following formula (3b): If the orientation function is too small, an acceptable single-unit transmittance and / or degree of polarization may not be obtained. -0.01x+0.50 <f<-0.018x+1.11 (3a) -0.01x+0.57 <f<-0.018x+1.1 (3b)

[0020] The orientation function (f) is determined, for example, by attenuated total reflection (ATR) measurement using a Fourier transform infrared spectrophotometer (FT-IR) and polarized light as the measurement light. Specifically, germanium is used as the crystallite to which the polarizer is attached, the incident angle of the measurement light is 45°, the incident polarized infrared light (measurement light) is polarized light (s-polarized light) that vibrates parallel to the surface to which the germanium crystal sample is attached, and the measurement is performed with the stretch direction of the polarizer arranged parallel and perpendicular to the polarization direction of the measurement light. -1 The intensity I is calculated according to the following formula using the intensity of 3330 cm -1 is used as the reference peak, and 2941 cm -1 / 3330cm -1 The value is 2941 cm. Note that f=1 is perfect alignment, and f=0 is random. -1 The peak is considered to be an absorption due to the vibration of the main chain (-CH2-) of PVA in the polarizer. f=(3 <cos 2 θ>-1) / 2 =(1-D) / [c(2D+1)] =-2×(1-D) / (2D+1) however, c = (3cos 2 β-1) / 2, 2941cm -1 For vibration, β=90°. θ: Angle of molecular chain to stretching direction β: Angle of the transition dipole moment with respect to the chain axis D=(I ⊥ ) / (I / / ) (In this case, the more the PVA molecules are oriented, the larger D becomes.) I ⊥ : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are perpendicular I / / : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are parallel

[0021] The thickness of the polarizer is preferably 10 μm or less, and more preferably 8 μm or less. The lower limit of the thickness of the polarizer may be, for example, 1 μm. The thickness of the polarizer may be 2 μm to 10 μm in one embodiment, and 2 μm to 8 μm in another embodiment. By making the thickness of the polarizer so thin, it is possible to make the thermal shrinkage very small. It is presumed that such a configuration may also contribute to suppressing the occurrence of cracks in the irregularly processed portion of the polarizing plate.

[0022] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is preferably 40.0% or more, more preferably 41.0% or more. The upper limit of the single transmittance may be, for example, 49.0%. In one embodiment, the single transmittance of the polarizer is 40.0% to 45.0%. The degree of polarization of the polarizer is preferably 99.0% or more, more preferably 99.4% or more. The upper limit of the degree of polarization may be, for example, 99.999%. In one embodiment, the degree of polarization of the polarizer is 99.0% to 99.9%. One feature of the polarizer according to the embodiment of the present invention is that the degree of orientation of the PVA-based resin constituting the polarizer is lower than that of a conventional polarizer, and the polarizer has the above-mentioned in-plane retardation, birefringence, and / or orientation function, yet the polarizer can achieve such a single transmittance and degree of polarization that are practically acceptable. This is presumably due to the manufacturing method described later. The single transmittance is typically a Y value measured using an ultraviolet-visible spectrophotometer and subjected to luminosity correction. The polarization degree is typically calculated by the following formula based on the parallel transmittance Tp and the crossed transmittance Tc measured using an ultraviolet-visible spectrophotometer and subjected to luminosity correction. Degree of polarization (%)={(Tp-Tc) / (Tp+Tc)} 1 / 2×100

[0023] The piercing strength of the polarizer is, for example, 30 gf / μm or more, preferably 35 gf / μm or more, more preferably 40 gf / μm or more, even more preferably 45 gf / μm or more, and particularly preferably 50 gf / μm or more. The upper limit of the piercing strength can be, for example, 80 gf / μm. By setting the piercing strength of the polarizer in such a range, it is possible to significantly suppress the occurrence of cracks in the irregularly processed part and the tearing of the polarizer along the absorption axis direction. As a result, a polarizer (and, as a result, a polarizing plate) with very excellent flexibility can be obtained. The piercing strength indicates the crack resistance of the polarizer when the polarizer is pierced with a predetermined strength. The piercing strength can be expressed, for example, as the strength (breaking strength) at which the polarizer breaks when a predetermined needle is attached to a compression tester and the needle is pierced into the polarizer at a predetermined speed. As is clear from the unit, the piercing strength means the piercing strength per unit thickness (1 μm) of the polarizer.

[0024] As described above, the polarizer is composed of a PVA-based resin film containing a dichroic material. Preferably, the PVA-based resin constituting the PVA-based resin film (substantially the polarizer) contains an acetoacetyl-modified PVA-based resin. With such a configuration, a polarizer having a desired piercing strength can be obtained. The blending amount of the acetoacetyl-modified PVA-based resin is preferably 5% by weight to 20% by weight, and more preferably 8% by weight to 12% by weight, when the entire PVA-based resin is taken as 100% by weight. If the blending amount is within such a range, the piercing strength can be set to a more suitable range.

[0025] A polarizer can be typically produced using a laminate of two or more layers. A specific example of a polarizer obtained using a laminate includes a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate, drying the resin substrate to form a PVA-based resin layer on the resin substrate, and obtaining a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch the laminate. Furthermore, the stretching preferably further includes stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In an embodiment of the present invention, the total stretching ratio is preferably 3.0 to 4.5 times, which is significantly smaller than normal. Even at such a total stretching ratio, a polarizer having acceptable optical properties can be obtained by adding a halide and combining it with a dry shrinkage treatment. Furthermore, in an embodiment of the present invention, the stretching ratio of the auxiliary air stretching is preferably larger than the stretching ratio of the boric acid water stretching. With this configuration, a polarizer having acceptable optical properties can be obtained even at a small total stretching ratio. In addition, the laminate is preferably subjected to a dry shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. In one embodiment, the method for producing a polarizer includes subjecting the laminate to an auxiliary air stretching treatment, a dyeing treatment, an underwater stretching treatment, and a dry shrinkage treatment in this order. By introducing the auxiliary stretching, even when a PVA-based resin is applied onto a thermoplastic resin, it is possible to increase the crystallinity of the PVA-based resin, and to achieve high optical properties. At the same time, by increasing the orientation of the PVA-based resin in advance, problems such as a decrease in the orientation of the PVA-based resin or dissolution when the resin is immersed in water in the subsequent dyeing and stretching processes can be prevented, making it possible to achieve high optical properties.Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation of polyvinyl alcohol molecules is disturbed and the orientation is reduced, compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of a polarizer obtained by immersing the laminate in a liquid through a treatment process such as a dyeing process and an underwater stretching process. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction through a drying shrinkage process. The obtained resin substrate / polarizer laminate may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or the resin substrate may be peeled off from the resin substrate / polarizer laminate and any suitable protective layer may be laminated on the peeled surface according to the purpose. Details of the method for producing a polarizer will be described in Section A-3.

[0026] A-3. Manufacturing method of polarizer The method for producing the polarizer preferably includes forming a polyvinyl alcohol-based resin layer (PVA-based resin layer) containing a halide and a polyvinyl alcohol-based resin (PVA-based resin) on one side of a long thermoplastic resin substrate to form a laminate, and subjecting the laminate to an auxiliary air stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order, in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. The content of the halide in the PVA-based resin layer is preferably 5 parts by weight to 20 parts by weight with respect to 100 parts by weight of the PVA-based resin. The drying shrinkage treatment is preferably performed using a heating roll, and the temperature of the heating roll is preferably 60° C. to 120° C. The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment is preferably 2% or more. Furthermore, the stretching ratio of the auxiliary air stretching is preferably larger than the stretching ratio of the underwater stretching. According to such a production method, the polarizer described in the above item A-2 can be obtained. In particular, a laminate including a PVA-based resin layer containing a halide is prepared, the laminate is stretched in multiple stages including auxiliary air stretching and underwater stretching, and the stretched laminate is heated with a heating roll to shrink the laminate by 2% or more in the width direction, thereby obtaining a polarizer having excellent optical properties (typically, single transmittance and polarization degree).

[0027] A-3-1. Preparation of laminate Any suitable method can be adopted as a method for producing a laminate of a thermoplastic resin substrate and a PVA-based resin layer. Preferably, a coating liquid containing a halide and a PVA-based resin is applied to the surface of the thermoplastic resin substrate, and then dried to form a PVA-based resin layer on the thermoplastic resin substrate. As described above, the content of the halide in the PVA-based resin layer is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA-based resin.

[0028] Any appropriate method can be used as the coating method of the coating liquid. For example, roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, knife coating (comma coating, etc.), etc. are listed. The coating and drying temperature of the coating liquid is preferably 50° C. or higher.

[0029] The thickness of the PVA-based resin layer is preferably 2 μm to 30 μm, and more preferably 2 μm to 20 μm. By making the thickness of the PVA-based resin layer before stretching very thin in this manner and reducing the total stretching ratio as described below, a polarizer having an acceptable single transmittance and polarization degree can be obtained despite the degree of orientation of the PVA-based resin being lower than in the past.

[0030] Before forming the PVA-based resin layer, the thermoplastic resin substrate may be subjected to a surface treatment (e.g., corona treatment, etc.), or an easy-adhesion layer may be formed on the thermoplastic resin substrate. By carrying out such treatment, the adhesion between the thermoplastic resin substrate and the PVA-based resin layer can be improved.

[0031] A-3-1-1. Thermoplastic resin base material Any suitable thermoplastic resin film may be used as the thermoplastic resin substrate. Details of the thermoplastic resin substrate are described in, for example, JP 2012-73580 A. The entire disclosure of this publication is incorporated herein by reference.

[0032] A-3-1-2. Coating solution The coating liquid contains a halide and a PVA resin as described above. The coating liquid is typically a solution in which the halide and the PVA resin are dissolved in a solvent. Examples of the solvent include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyhydric alcohols such as trimethylolpropane, and amines such as ethylenediamine and diethylenetriamine. These can be used alone or in combination of two or more. Among these, water is preferred. The concentration of the PVA resin in the solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. With such a resin concentration, a uniform coating film that is in close contact with the thermoplastic resin substrate can be formed. The content of the halide in the coating liquid is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA resin.

[0033] Additives may be added to the coating liquid. Examples of additives include plasticizers and surfactants. Examples of plasticizers include polyhydric alcohols such as ethylene glycol and glycerin. Examples of surfactants include nonionic surfactants. These can be used to further improve the uniformity, dyeability, and stretchability of the resulting PVA-based resin layer.

[0034] Any appropriate resin may be adopted as the PVA-based resin. Examples include polyvinyl alcohol and ethylene-vinyl alcohol copolymer. Polyvinyl alcohol is obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer is obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of the PVA-based resin is usually 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. The saponification degree can be determined in accordance with JIS K 6726-1994. By using a PVA-based resin having such a saponification degree, a polarizer having excellent durability can be obtained. If the saponification degree is too high, gelation may occur. As described above, the PVA-based resin preferably contains an acetoacetyl-modified PVA-based resin.

[0035] The average degree of polymerization of the PVA resin can be appropriately selected depending on the purpose. The average degree of polymerization is usually 1000 to 10000, preferably 1200 to 4500, and more preferably 1500 to 4300. The average degree of polymerization can be determined in accordance with JIS K 6726-1994.

[0036] Any suitable halide may be used as the halide. For example, iodide and sodium chloride may be used. For example, iodide may be potassium iodide, sodium iodide, and lithium iodide. Among these, potassium iodide is preferred.

[0037] The amount of the halide in the coating solution is preferably 5 to 20 parts by weight per 100 parts by weight of the PVA-based resin, and more preferably 10 to 15 parts by weight per 100 parts by weight of the PVA-based resin. If the amount of the halide exceeds 20 parts by weight per 100 parts by weight of the PVA-based resin, the halide may bleed out, causing the finally obtained polarizer to become cloudy.

[0038] Generally, the orientation of polyvinyl alcohol molecules in the PVA-based resin layer increases when the PVA-based resin layer is stretched, but when the stretched PVA-based resin layer is immersed in a liquid containing water, the orientation of polyvinyl alcohol molecules may be disturbed and the orientation may decrease. In particular, when a laminate of a thermoplastic resin substrate and a PVA-based resin layer is stretched in boric acid water, the tendency of the orientation degree to decrease is significant when the laminate is stretched in boric acid water at a relatively high temperature to stabilize the stretching of the thermoplastic resin substrate. For example, the stretching of a PVA film alone in boric acid water is generally performed at 60°C, whereas the stretching of a laminate of A-PET (thermoplastic resin substrate) and a PVA-based resin layer is performed at a high temperature of about 70°C, in which case the orientation of PVA at the initial stage of stretching may decrease before it increases due to underwater stretching. In response to this, a laminate of a PVA-based resin layer containing a halide and a thermoplastic resin substrate is prepared, and the laminate is stretched at high temperature (auxiliary stretching) in air before being stretched in boric acid water, so that the crystallization of the PVA-based resin in the PVA-based resin layer of the laminate after the auxiliary stretching can be promoted. As a result, when the PVA-based resin layer is immersed in a liquid, the orientation of the polyvinyl alcohol molecules is disturbed and the orientation is reduced, compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of a polarizer obtained by immersing the laminate in a liquid through a process such as a dyeing process and an underwater stretching process.

[0039] A-3-2. Aerial supplementary stretching process In particular, in order to obtain high optical properties, a two-stage stretching method is selected, which combines dry stretching (auxiliary stretching) and stretching in boric acid water. By introducing auxiliary stretching like two-stage stretching, it is possible to stretch while suppressing the crystallization of the thermoplastic resin substrate. Furthermore, when applying a PVA-based resin on a thermoplastic resin substrate, it is necessary to lower the application temperature compared to when applying a PVA-based resin on a normal metal drum in order to suppress the influence of the glass transition temperature of the thermoplastic resin substrate, and as a result, the crystallization of the PVA-based resin becomes relatively low, and a problem that sufficient optical properties cannot be obtained may occur. On the other hand, by introducing auxiliary stretching, it is possible to increase the crystallinity of the PVA-based resin even when applying a PVA-based resin on a thermoplastic resin, and it is possible to achieve high optical properties. At the same time, by increasing the orientation of the PVA-based resin in advance, problems such as a decrease in the orientation of the PVA-based resin or dissolution can be prevented when immersed in water in the subsequent dyeing process or stretching process, and it is possible to achieve high optical properties.

[0040] The stretching method of the auxiliary air stretching may be fixed end stretching (for example, a method of stretching using a tenter stretching machine) or free end stretching (for example, a method of uniaxially stretching a laminate between rolls with different peripheral speeds), but in order to obtain high optical properties, free end stretching may be actively adopted. In one embodiment, the air stretching process includes a heated roll stretching process in which the laminate is stretched by the difference in peripheral speed between heated rolls while being transported in its longitudinal direction. The air stretching process typically includes a zone stretching process and a heated roll stretching process. The order of the zone stretching process and the heated roll stretching process is not limited, and the zone stretching process may be performed first, or the heated roll stretching process may be performed first. The zone stretching process may be omitted. In one embodiment, the zone stretching process and the heated roll stretching process are performed in this order. In another embodiment, the film is stretched by gripping the film end in a tenter stretching machine and widening the distance between the tenters in the flow direction (the widening of the distance between the tenters is the stretching ratio). At this time, the distance of the tenter in the width direction (perpendicular to the machine direction) is set to be as close as possible. Preferably, it can be set to be as close as possible to the free end stretching ratio in the machine direction. In the case of free end stretching, the shrinkage ratio in the width direction = (1 / stretching ratio) 1 / 2 It is calculated as follows.

[0041] The auxiliary air-drawing may be performed in one step or in multiple steps. When the auxiliary air-drawing is performed in multiple steps, the draw ratio is the product of the draw ratios in each step. The draw direction in the auxiliary air-drawing is preferably approximately the same as the draw direction in the underwater drawing.

[0042] The stretching ratio in the auxiliary air stretching is preferably 1.0 to 4.0 times, more preferably 1.5 to 3.5 times, and further preferably 2.0 to 3.0 times. If the stretching ratio of the auxiliary air stretching is in such a range, the total stretching ratio can be set in a desired range when combined with underwater stretching, and desired birefringence, in-plane retardation, and / or orientation function can be realized. As a result, a polarizer (and consequently a polarizing plate) in which crack generation in the irregularly processed portion is suppressed can be obtained. Furthermore, as described above, the stretching ratio of the auxiliary air stretching is preferably larger than the stretching ratio of the underwater stretching. With such a configuration, a polarizer having acceptable optical properties can be obtained even if the total stretching ratio is small. More specifically, the ratio of the stretching ratio of the auxiliary air stretching to the stretching ratio of the underwater stretching (underwater stretching / auxiliary air stretching) is preferably 0.4 to 0.9, and more preferably 0.5 to 0.8.

[0043] The stretching temperature of the auxiliary in-air stretching can be set to any appropriate value depending on the material of the thermoplastic resin substrate, the stretching method, etc. The stretching temperature is preferably equal to or higher than the glass transition temperature (Tg) of the thermoplastic resin substrate, more preferably equal to or higher than the glass transition temperature (Tg) of the thermoplastic resin substrate + 10°C, and particularly preferably equal to or higher than Tg + 15°C. On the other hand, the upper limit of the stretching temperature is preferably 170°C. By stretching at such a temperature, rapid crystallization of the PVA resin can be suppressed, and defects due to the crystallization (for example, the orientation of the PVA resin layer due to stretching is hindered) can be suppressed.

[0044] A-3-3. Insolubilization, dyeing and crosslinking treatments If necessary, after the auxiliary air stretching treatment, an insolubilization treatment is performed before the underwater stretching treatment or the dyeing treatment. The insolubilization treatment is typically performed by immersing the PVA-based resin layer in an aqueous boric acid solution. The dyeing treatment is typically performed by dyeing the PVA-based resin layer with a dichroic substance (typically iodine). If necessary, after the dyeing treatment, a crosslinking treatment is performed before the underwater stretching treatment. The crosslinking treatment is typically performed by immersing the PVA-based resin layer in an aqueous boric acid solution. Details of the insolubilization treatment, the dyeing treatment, and the crosslinking treatment are described in, for example, JP 2012-73580 A.

[0045] A-3-4. Underwater stretching treatment The underwater stretching treatment is performed by immersing the laminate in a stretching bath. According to the underwater stretching treatment, the laminate can be stretched at a temperature lower than the glass transition temperature (typically about 80° C.) of the thermoplastic resin substrate or the PVA-based resin layer, and the PVA-based resin layer can be stretched while suppressing crystallization. As a result, a polarizer having excellent optical properties can be produced.

[0046] The stretching method of the laminate can be any appropriate method. Specifically, it may be fixed end stretching or free end stretching (for example, a method of uniaxially stretching the laminate by passing it between rolls having different peripheral speeds). Preferably, free end stretching is selected. The stretching of the laminate may be performed in one stage or multiple stages. When performing multiple stages, the total stretching ratio is the product of the stretching ratios in each stage.

[0047] The underwater stretching is preferably performed by immersing the laminate in an aqueous solution of boric acid (stretching in boric acid water). By using an aqueous solution of boric acid as a stretching bath, it is possible to impart to the PVA-based resin layer rigidity that can withstand the tension applied during stretching and water resistance that does not dissolve in water. Specifically, boric acid can generate tetrahydroxyborate anions in the aqueous solution and crosslink with the PVA-based resin through hydrogen bonds. As a result, it is possible to impart rigidity and water resistance to the PVA-based resin layer and stretch it well, and to produce a polarizer with excellent optical properties.

[0048] The boric acid aqueous solution is preferably obtained by dissolving boric acid and / or a borate in water as a solvent. The boric acid concentration is preferably 1 to 10 parts by weight, more preferably 2.5 to 6 parts by weight, and particularly preferably 3 to 5 parts by weight, relative to 100 parts by weight of water. By setting the boric acid concentration to 1 part by weight or more, dissolution of the PVA-based resin layer can be effectively suppressed, and a polarizer with higher characteristics can be produced. In addition to boric acid or a borate, an aqueous solution obtained by dissolving a boron compound such as borax, glyoxal, glutaraldehyde, or the like in a solvent can also be used.

[0049] Preferably, an iodide is added to the stretching bath (boric acid aqueous solution). By adding an iodide, it is possible to suppress the elution of iodine adsorbed in the PVA resin layer. Specific examples of the iodide are as described above. The concentration of the iodide is preferably 0.05 to 15 parts by weight, more preferably 0.5 to 8 parts by weight, relative to 100 parts by weight of water.

[0050] The stretching temperature (liquid temperature of the stretching bath) is preferably 40°C to 85°C, more preferably 60°C to 75°C. At such a temperature, the laminate can be stretched at a high ratio while suppressing dissolution of the PVA-based resin layer. Specifically, as described above, the glass transition temperature (Tg) of the thermoplastic resin substrate is preferably 60°C or higher in relation to the formation of the PVA-based resin layer. In this case, if the stretching temperature is lower than 40°C, there is a risk that the substrate cannot be stretched well even when the plasticization of the thermoplastic resin substrate by water is taken into consideration. On the other hand, the higher the temperature of the stretching bath, the higher the solubility of the PVA-based resin layer, and there is a risk that excellent optical properties cannot be obtained. The immersion time of the laminate in the stretching bath is preferably 15 seconds to 5 minutes.

[0051] The stretching ratio in underwater stretching is preferably 1.0 to 2.2 times, more preferably 1.1 to 2.0 times, further preferably 1.1 to 1.8 times, and even more preferably 1.2 to 1.6 times. When the stretching ratio in underwater stretching is in such a range, the total stretching ratio can be set in a desired range, and the desired birefringence, in-plane retardation, and / or orientation function can be realized. As a result, a polarizer (and, as a result, a polarizing plate) in which crack generation in the irregularly shaped processed portion is suppressed can be obtained. As described above, the total stretching ratio (the total stretching ratio when the auxiliary air stretching and the underwater stretching are combined) is preferably 3.0 to 4.5 times, more preferably 3.0 to 4.3 times, and further preferably 3.0 to 4.0 times, relative to the original length of the laminate. By appropriately combining the addition of a halide to the coating solution, the adjustment of the stretching ratios of the auxiliary air stretching and the underwater stretching, and the drying shrinkage treatment, a polarizer having acceptable optical properties can be obtained even at such a total stretching ratio.

[0052] A-3-5. Drying shrinkage treatment The drying shrinkage treatment may be performed by zone heating in which the entire zone is heated, or by heating the transport roll (using a so-called heating roll) (heat roll drying method). Preferably, both are used. By drying using a heating roll, it is possible to efficiently suppress the heat curl of the laminate and produce a polarizer with excellent appearance. Specifically, by drying the laminate in a state where it is aligned with the heating roll, it is possible to efficiently promote the crystallization of the thermoplastic resin substrate and increase the crystallinity, and even at a relatively low drying temperature, it is possible to satisfactorily increase the crystallinity of the thermoplastic resin substrate. As a result, the rigidity of the thermoplastic resin substrate increases and it becomes in a state where it can withstand the shrinkage of the PVA-based resin layer due to drying, and curling is suppressed. In addition, by using a heating roll, it is possible to dry the laminate while maintaining it in a flat state, so that it is possible to suppress not only curling but also the occurrence of wrinkles. At this time, the optical properties of the laminate can be improved by shrinking it in the width direction by the drying shrinkage treatment. This is because the orientation of the PVA and the PVA / iodine complex can be effectively increased. The shrinkage percentage in the width direction of the laminate due to the drying shrinkage treatment is preferably 1% to 10%, more preferably 2% to 8%, and particularly preferably 2% to 6%.

[0053] 6 is a schematic diagram showing an example of the drying shrinkage treatment. In the drying shrinkage treatment, the laminate 200 is dried while being transported by transport rolls R1 to R6 heated to a predetermined temperature and guide rolls G1 to G4. In the illustrated example, the transport rolls R1 to R6 are arranged so as to alternately and continuously heat the surface of the PVA resin layer and the surface of the thermoplastic resin substrate, but, for example, the transport rolls R1 to R6 may be arranged so as to continuously heat only one surface of the laminate 200 (for example, the thermoplastic resin substrate surface).

[0054] Drying conditions can be controlled by adjusting the heating temperature of the transport rolls (temperature of the heating rolls), the number of heating rolls, the contact time with the heating rolls, etc. The temperature of the heating rolls is preferably 60°C to 120°C, more preferably 65°C to 100°C, and particularly preferably 70°C to 80°C. The crystallinity of the thermoplastic resin can be favorably increased, curling can be favorably suppressed, and an optical laminate with extremely excellent durability can be produced. The temperature of the heating rolls can be measured by a contact thermometer. In the illustrated example, six transport rolls are provided, but there is no particular restriction as long as there are multiple transport rolls. The number of transport rolls is usually 2 to 40, preferably 4 to 30. The contact time (total contact time) between the laminate and the heating rolls is preferably 1 to 300 seconds, more preferably 1 to 20 seconds, and even more preferably 1 to 10 seconds.

[0055] The heating roll may be provided in a heating furnace (for example, an oven) or in a normal production line (under room temperature environment). It is preferably provided in a heating furnace equipped with a blowing means. By using drying with a heating roll in combination with hot air drying, it is possible to suppress abrupt temperature changes between the heating rolls, and it is possible to easily control shrinkage in the width direction. The hot air drying temperature is preferably 30°C to 100°C. The hot air drying time is preferably 1 second to 300 seconds. The hot air speed is preferably about 10 m / s to 30 m / s. The wind speed is the wind speed in the heating furnace, and can be measured by a mini-vane type digital anemometer.

[0056] A-3-6. Other processing Preferably, after the underwater stretching treatment and before the drying shrinkage treatment, a washing treatment is carried out. The washing treatment is typically carried out by immersing the PVA-based resin layer in an aqueous potassium iodide solution.

[0057] A-4.Protective layer The thickness of the protective layer is 10 μm or less. The thickness of the protective layer of 10 μm or less can contribute to the thinning of the polarizing plate. Conventionally, a protective layer having a thickness of 20 μm or more has been used in order to protect the polarizer by following the shrinkage of the polarizer when heated. In contrast, the polarizer used in the embodiment of the present invention has a lower degree of orientation of the PVA resin than conventional polarizers as described above, and as a result, shrinkage due to heating is small, so that even when a protective layer having a thickness of 10 μm or less is used, the occurrence of cracks during heating is suppressed. Furthermore, such a polarizer can also contribute to the suppression of cracks in the irregularly shaped portion.

[0058] The thickness of the protective layer is preferably 7 μm or less, more preferably 5 μm or less, and further preferably 3 μm or less. The thickness of the protective layer is, for example, 1 μm or more.

[0059] The protective layer is composed of a resin film. As the resin forming the resin film, any appropriate resin can be used depending on the purpose. Specific examples include thermoplastic resins such as (meth)acrylic, cellulose such as triacetyl cellulose (TAC), polyester, polyurethane, polyvinyl alcohol, polycarbonate, polyamide, polyimide, polyethersulfone, polysulfone, polystyrene, polynorbornene, polyolefin, and acetate; thermosetting resins or active energy ray curing resins such as (meth)acrylic, urethane, (meth)acrylic urethane, epoxy, and silicone; and glassy polymers such as siloxane polymers. In one embodiment, examples of the resin forming the resin film include epoxy resins and (meth)acrylic resins. These may be used alone or in combination.

[0060] The resin film constituting the protective layer may be, for example, a molded product of a molten resin, a solidified product of a coating film of a resin solution obtained by dissolving or dispersing a resin in an aqueous solvent or an organic solvent, or a cured product of a curable resin (for example, a photocationically cured product).

[0061] In one embodiment, the protective layer may be a solidified coating film of an organic solvent solution of a thermoplastic (meth)acrylic resin (hereinafter, the (meth)acrylic resin may be simply referred to as an "acrylic resin"), a photocationically cured product of an epoxy resin, or a solidified coating film of an organic solvent solution of an epoxy resin. A specific description will be given below.

[0062] A-4-1.Solidified coating of organic solvent solution of thermoplastic acrylic resin In one embodiment, the protective layer is composed of a solidified coating film of a solution of a thermoplastic acrylic resin in an organic solvent. The softening temperature of the protective layer in this embodiment is preferably 100°C or higher, more preferably 115°C or higher, even more preferably 120°C or higher, and particularly preferably 125°C or higher from the viewpoint of humidification durability, and is preferably 300°C or lower, more preferably 250°C or lower, even more preferably 200°C or lower, and particularly preferably 160°C or lower from the viewpoint of moldability.

[0063] The acrylic resin preferably has a glass transition temperature (Tg) of 100° C. or higher. As a result, the softening temperature of the protective layer is also approximately 100° C. or higher. If the Tg of the acrylic resin is 100° C. or higher, a polarizing plate including a protective layer obtained from such a resin can have excellent humidification durability in addition to crack resistance. The Tg of the acrylic resin is more preferably 110° C. or higher, further preferably 115° C. or higher, even more preferably 120° C. or higher, and particularly preferably 125° C. or higher. On the other hand, the Tg of the acrylic resin is preferably 300° C. or lower, more preferably 250° C. or lower, further preferably 200° C. or lower, and particularly preferably 160° C. or lower. If the Tg of the acrylic resin is in such a range, it can have excellent moldability.

[0064] As the acrylic resin, any appropriate acrylic resin may be adopted as long as it has the above Tg. The acrylic resin typically contains alkyl(meth)acrylate as a main component as a monomer unit (repeating unit). In this specification, "(meth)acrylic" means acrylic and / or methacrylic. Examples of the alkyl(meth)acrylate constituting the main skeleton of the acrylic resin include linear or branched alkyl groups having 1 to 18 carbon atoms. These can be used alone or in combination. Furthermore, any appropriate copolymerization monomer may be introduced into the acrylic resin by copolymerization. By appropriately setting the type, number, combination and compounding ratio of the alkyl(meth)acrylate, the type, number, combination and compounding ratio of the copolymerization monomer, and the polymerization conditions, an acrylic resin capable of forming a desired protective layer can be obtained.

[0065] The acrylic resin preferably has a repeating unit containing a ring structure. Examples of the repeating unit containing a ring structure include a lactone ring unit, a glutaric anhydride unit, a glutarimide unit, a maleic anhydride unit, and a maleimide (N-substituted maleimide) unit. The repeating unit containing a ring structure may contain only one type of repeating unit, or may contain two or more types. An acrylic resin having a lactone ring unit is described in, for example, JP 2008-181078 A. Acrylic resins having glutarimide units are described, for example, in JP-A-2006-309033, JP-A-2006-317560, JP-A-2006-328334, JP-A-2006-337491, JP-A-2006-337492, JP-A-2006-337493, and JP-A-2006-337569. The descriptions in these publications are incorporated herein by reference.

[0066] The content of the repeating unit containing a ring structure in the acrylic resin is preferably 1 mol% to 50 mol%, more preferably 10 mol% to 40 mol%, and even more preferably 20 mol% to 30 mol%. If the content is too low, Tg may be less than 100°C, and the heat resistance, solvent resistance, and surface hardness of the resulting protective layer may be insufficient. If the content is too high, moldability and transparency may be insufficient.

[0067] In the embodiment of the present invention, the acrylic resin may be used in combination with other resins. That is, a monomer component constituting the acrylic resin may be copolymerized with a monomer component constituting the other resin, and the copolymer may be used to form a protective layer, which will be described later; or a blend of the acrylic resin and other resin may be used to form a protective layer.

[0068] The protective layer of the present embodiment can be formed, for example, by applying a solution of an acrylic resin in an organic solvent onto the surface of a polarizer to form a coating film, and then solidifying the coating film.

[0069] As the organic solvent, any suitable organic solvent capable of dissolving or uniformly dispersing the acrylic resin can be used. Specific examples of the organic solvent include ethyl acetate, toluene, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclopentanone, and cyclohexanone.

[0070] The concentration of the acrylic resin in the solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. With such a resin concentration, a uniform coating film that is in close contact with the polarizer can be formed.

[0071] The solution may be applied to any suitable substrate or to a polarizer. When the solution is applied to a substrate, the solidified coating film formed on the substrate is transferred to the polarizer. When the solution is applied to a polarizer, the coating film is dried (solidified) to form a protective layer directly on the polarizer. Preferably, the solution is applied to a polarizer, and a protective layer is directly formed on the polarizer. With this configuration, the adhesive layer or pressure-sensitive adhesive layer required for transfer can be omitted, so that the polarizing plate can be made even thinner. Any suitable method can be adopted as a method for applying the solution. Specific examples include roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, and knife coating (comma coating, etc.).

[0072] A protective layer can be formed by drying (solidifying) the coating film of the solution. The drying temperature is preferably 100° C. or less, and more preferably 50° C. to 70° C. If the drying temperature is within this range, adverse effects on the polarizer can be prevented. The drying time can vary depending on the drying temperature. The drying time can be, for example, 1 minute to 10 minutes.

[0073] A-4-2. Photo-cured epoxy resin In one embodiment, the protective layer is composed of a photocationically cured product of an epoxy resin. By using such a protective layer, the occurrence of cracks can be suppressed and excellent humidification durability can be obtained. As described above, since the protective layer is a photocationically cured product, the composition for forming the protective layer contains a photocationic polymerization initiator. The photocationic polymerization initiator is a photosensitive agent having a function of a photoacid generator, and a representative example is an ionic onium salt consisting of a cationic portion and an anionic portion. In this onium salt, the cationic portion absorbs light, and the anionic portion serves as a source of acid generation. The acid generated from this photocationic polymerization initiator causes ring-opening polymerization of the epoxy group. The protective layer, which is the obtained photocationically cured product, has a high softening temperature and can reduce the amount of iodine adsorption. Therefore, it is possible to provide a polarizing plate that is suppressed from causing cracks and has excellent humidification durability.

[0074] From the viewpoint of humid durability, the softening temperature of the protective layer in this embodiment is preferably 100°C or higher, more preferably 110°C or higher, even more preferably 120°C or higher, and particularly preferably 125°C or higher, and from the viewpoint of formability, it is preferably 300°C or lower, more preferably 250°C or lower, even more preferably 200°C or lower, and particularly preferably 160°C or lower.

[0075] A-4-2-1.Epoxy resin Any suitable epoxy resin can be used as the epoxy resin, and an epoxy resin having an aromatic ring or an alicyclic ring can be preferably used. In this embodiment, an epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton can be preferably used. Examples of the aromatic skeleton include a benzene ring, a naphthalene ring, and a fluorene ring. Only one type of epoxy resin may be used, or two or more types may be used in combination. Preferably, an epoxy resin having a biphenyl skeleton or a bisphenol skeleton as the aromatic skeleton, or a hydrogenated product thereof, is used. By using such an epoxy resin, a polarizing plate having better durability and excellent flexibility can be provided.

[0076] In one embodiment, the epoxy resin having a biphenyl skeleton is an epoxy resin having the following structure: The epoxy resin having a biphenyl skeleton may be used alone or in combination of two or more kinds. [ka] (In the formula, R 14 ~R 21 each independently represents a hydrogen atom, a linear or branched, substituted or unsubstituted hydrocarbon group having 1 to 12 carbon atoms, or a halogen element).

[0077] In one embodiment, the epoxy resin having a biphenyl skeleton is an epoxy resin represented by the following formula: [ka] (In the formula, R 14 ~R 21 is as above, and n represents an integer of 0 to 6).

[0078] In one embodiment, the epoxy resin having a biphenyl skeleton is an epoxy resin having only a biphenyl skeleton. By using an epoxy resin having only a biphenyl skeleton, the durability of the obtained protective layer can be further improved. In another embodiment, the epoxy resin having a biphenyl skeleton may contain a chemical structure other than the biphenyl skeleton. Examples of the chemical structure other than the biphenyl skeleton include a bisphenol skeleton, an alicyclic structure, and an aromatic ring structure. In this case, the proportion (molar ratio) of the chemical structure other than the biphenyl skeleton is preferably smaller than that of the biphenyl skeleton.

[0079] The epoxy resin (epoxy resin after photocationic curing) preferably has a glass transition temperature (Tg) of 100° C. or higher. As a result, the softening temperature of the protective layer is also approximately 100° C. or higher. If the Tg of the epoxy resin is 100° C. or higher, the polarizing plate including the obtained protective layer is likely to have excellent durability. The Tg of the epoxy resin is more preferably 110° C. or higher, further preferably 120° C. or higher, and particularly preferably 125° C. or higher. On the other hand, the Tg of the epoxy resin is preferably 300° C. or lower, more preferably 250° C. or lower, further preferably 200° C. or lower, and particularly preferably 160° C. or lower. If the Tg of the epoxy resin is within such a range, excellent moldability can be obtained.

[0080] The epoxy equivalent of the epoxy resin is preferably 100 g / equivalent or more, more preferably 150 g / equivalent or more, and even more preferably 200 g / equivalent or more. The epoxy equivalent of the epoxy resin is preferably 3000 g / equivalent or less, more preferably 2500 g / equivalent or less, and even more preferably 2000 g / equivalent or less. By having the epoxy equivalent in the above range, a more stable protective layer (a protective layer with less residual monomer and sufficiently cured) can be obtained. In this specification, the term "epoxy equivalent" refers to the "mass of an epoxy resin containing one equivalent of epoxy group" and can be measured in accordance with JIS K 7236.

[0081] In this embodiment, the epoxy resin may be used in combination with other resins. That is, a blend of the epoxy resin (e.g., an epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton) with other resins may be used to form the protective layer. Examples of the other resins include acrylic resins and oxetane resins.

[0082] Any suitable (meth)acrylic compound can be used as the acrylic resin. For example, the (meth)acrylic compound includes, for example, a (meth)acrylic compound having one (meth)acryloyl group in the molecule (hereinafter also referred to as a "monofunctional (meth)acrylic compound") and a (meth)acrylic compound having two or more (meth)acryloyl groups in the molecule (hereinafter also referred to as a "polyfunctional (meth)acrylic compound"). These (meth)acrylic compounds may be used alone or in combination of two or more. These acrylic resins are described, for example, in JP 2019-168500 A. The entire disclosure of this publication is incorporated herein by reference.

[0083] As the oxetane resin, any suitable compound having one or more oxetanyl groups in the molecule can be used. Examples of the oxetane compounds include oxetane compounds having one oxetanyl group in the molecule, such as 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-(phenoxymethyl)oxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(oxiranylmethoxy)oxetane, and (3-ethyloxetan-3-yl)methyl (meth)acrylate; and oxetane compounds having two or more oxetanyl groups in the molecule, such as 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, 1,4-bis[(3-ethyl-3-oxetanyl)methoxymethyl]benzene, and 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl. These oxetane resins may be used alone or in combination of two or more. As the oxetane resin, 3-ethyl-3-hydroxymethyloxetane, 1,4-bis[(3-ethyl-3-oxetanyl)methoxymethyl]benzene, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-(oxiranylmethoxy)oxetane, (3-ethyloxetan-3-yl)methyl (meth)acrylate, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, etc. are preferably used. These oxetane resins are easily available and can be excellent in dilution (low viscosity) and compatibility.

[0084] In one embodiment, from the viewpoint of compatibility and adhesiveness, an oxetane resin having a molecular weight of 500 or less and being liquid at room temperature (25° C.) is used. In one embodiment, an oxetane compound containing two or more oxetanyl groups in the molecule, an oxetane compound containing one oxetanyl group and one (meth)acryloyl group or one epoxy group in the molecule is preferably used, and more preferably 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, 3-ethyl-3-(oxiranylmethoxy)oxetane, or (3-ethyloxetan-3-yl)methyl (meth)acrylate is used. By using these oxetane resins, the curability and durability of the protective layer can be improved.

[0085] A-4-2-2. Photocationic polymerization initiator The photocationic polymerization initiator is a photosensitive agent having the function of a photoacid generator, and a representative example is an ionic onium salt consisting of a cationic portion and an anionic portion. In this onium salt, the cationic portion absorbs light, and the anionic portion serves as a source of acid generation. The acid generated from this photocationic polymerization initiator causes ring-opening polymerization of the epoxy group. As the photocationic polymerization initiator, any suitable compound that can cure an epoxy resin having at least one selected from the group consisting of an aromatic skeleton and a hydrogenated aromatic skeleton by irradiation with light such as ultraviolet light can be used. Only one type of photocationic polymerization initiator may be used, or two or more types may be used in combination.

[0086] Examples of the photocationic polymerization initiator include triphenylsulfonium hexafluoroantimonate, triphenylsulfonium hexafluorophosphate, p-(phenylthio)phenyl diphenylsulfonium hexafluoroantimonate, p-(phenylthio)phenyl diphenylsulfonium hexafluorophosphate, 4-chlorophenyl diphenylsulfonium hexafluorophosphate, 4-chlorophenyl diphenylsulfonium hexafluoroantimonate, bis[4-(diphenylsulfonio)phenyl]sulfide bishexafluorophosphate, bis[4-(diphenylsulfonio)phenyl]sulfide bishexafluoroantimonate, (2,4-cyclopentadiene-1-yl)[(1-methylethyl)benzene]-Fe-hexafluorophosphate, and diphenyliodonium hexafluoroantimonate. Preferably, a triphenylsulfonium salt-based hexafluoroantimonate type photocationic polymerization initiator or a diphenyliodonium salt-based hexafluoroantimonate type photocationic polymerization initiator is used.

[0087] The protective layer of the present embodiment can be formed, for example, by applying a composition containing the above-mentioned epoxy resin and a photocationic polymerization initiator to form a coating film, and then irradiating the coating film with light (for example, ultraviolet light).

[0088] The epoxy resin concentration in the composition is preferably 10 parts by weight to 30 parts by weight relative to 100 parts by weight of the solvent. With such a resin concentration, a uniform coating film that adheres closely to the polarizer can be formed.

[0089] The composition may be applied to any suitable substrate or to a polarizer. When the composition is applied to a substrate, the cured product of the coating film formed on the substrate is transferred to the polarizer. When the composition is applied to a polarizer, the coating film is cured, for example, by light irradiation, to directly form a protective layer on the polarizer. Preferably, the composition is applied to a polarizer, and a protective layer is directly formed on the polarizer. With this configuration, the adhesive layer or pressure-sensitive adhesive layer required for transfer can be omitted, so that the polarizing plate can be made even thinner. The method of applying the composition is as described above.

[0090] The curing of the coating film can be carried out by irradiating light (typically ultraviolet light) using any suitable light source to achieve any suitable irradiation amount. After the light irradiation, a heat treatment may be further carried out to complete the curing by the photoreaction. The heat treatment can be carried out at any suitable temperature and time.

[0091] A-4-3.Solidified coating of epoxy resin in organic solvent solution In one embodiment, the protective layer is composed of a solidified coating film of an organic solvent solution of an epoxy resin. The softening temperature of the protective layer in this embodiment is preferably 100° C. or higher, more preferably 110° C. or higher, even more preferably 120° C. or higher, and particularly preferably 125° C. or higher from the viewpoint of humidification durability, and is preferably 300° C. or lower, more preferably 250° C. or lower, even more preferably 200° C. or lower, and particularly preferably 160° C. or lower from the viewpoint of moldability.

[0092] A-4-3-1.Epoxy resin In this embodiment, the epoxy resin preferably has a glass transition temperature (Tg) of 100° C. or higher. As a result, the softening temperature of the protective layer is also approximately 100° C. or higher. If the Tg of the epoxy resin is 100° C. or higher, a polarizing plate including a protective layer obtained from such a resin is likely to have excellent durability. The Tg of the epoxy resin is more preferably 110° C. or higher, further preferably 120° C. or higher, and particularly preferably 125° C. or higher. On the other hand, the Tg of the epoxy resin is preferably 300° C. or lower, more preferably 250° C. or lower, further preferably 200° C. or lower, and particularly preferably 160° C. or lower. If the Tg of the epoxy resin is within such a range, it can have excellent moldability.

[0093] As the epoxy resin, any suitable epoxy resin may be adopted as long as it has the above-mentioned Tg. The epoxy resin typically refers to a resin having an epoxy group in its molecular structure. As the epoxy resin, an epoxy resin having an aromatic ring in its molecular structure is preferably used. By using an epoxy resin having an aromatic ring, an epoxy resin having a higher Tg can be obtained. Examples of the aromatic ring in the epoxy resin having an aromatic ring in its molecular structure include a benzene ring, a naphthalene ring, and a fluorene ring. Only one type of epoxy resin may be used, or two or more types may be used in combination. When two or more types of epoxy resins are used, an epoxy resin having an aromatic ring and an epoxy resin not having an aromatic ring may be used in combination.

[0094] Specific examples of epoxy resins having an aromatic ring in the molecular structure include bisphenol A diglycidyl ether type epoxy resins, bisphenol F diglycidyl ether type epoxy resins, bisphenol S diglycidyl ether type epoxy resins, resorcinol diglycidyl ether type epoxy resins, hydroquinone diglycidyl ether type epoxy resins, terephthalic acid diglycidyl ester type epoxy resins, bisphenoxyethanol fluorene diglycidyl ether type epoxy resins, bisphenol fluorene diglycidyl ether type epoxy resins, and biscresol fluorene diglycidyl ether type epoxy resins. Examples of epoxy resins include epoxy resins having two epoxy groups such as phenol-type epoxy resins; epoxy resins having three epoxy groups such as novolac-type epoxy resins, N,N,O-triglycidyl-P- or -m-aminophenol-type epoxy resins, N,N,O-triglycidyl-4-amino-m- or -5-amino-o-cresol-type epoxy resins, and 1,1,1-(triglycidyloxyphenyl)methane-type epoxy resins; and epoxy resins having four epoxy groups such as glycidylamine-type epoxy resins (e.g., diaminodiphenylmethane type, diaminodiphenylsulfone type, and metaxylenediamine type). In addition, glycidyl ester-type epoxy resins such as hexahydrophthalic anhydride-type epoxy resins, tetrahydrophthalic anhydride-type epoxy resins, dimer acid-type epoxy resins, and p-oxybenzoic acid-type epoxy resins may also be used.

[0095] The epoxy equivalent of the epoxy resin is preferably 1000 g / equivalent or more, more preferably 3000 g / equivalent or more, and even more preferably 5000 g / equivalent or more. The epoxy equivalent of the epoxy resin is preferably 30000 g / equivalent or less, more preferably 25000 g / equivalent or less, and even more preferably 20000 g / equivalent or less. By setting the epoxy equivalent within the above range, a more stable protective layer can be obtained. In this specification, the term "epoxy equivalent" refers to the "mass of an epoxy resin containing one equivalent of epoxy groups" and can be measured in accordance with JIS K 7236.

[0096] In this embodiment, the epoxy resin may be used in combination with other resins. That is, a blend of the epoxy resin and other resins may be used to form the protective layer. The other resins may be appropriately selected depending on the purpose.

[0097] The protective layer of the present embodiment can be formed, for example, by applying an organic solvent solution containing the epoxy resin to form a coating film, and then solidifying the coating film. The epoxy resin concentration in the organic solvent solution is preferably 3 parts by weight to 20 parts by weight per 100 parts by weight of the solvent. With such a resin concentration, a uniform coating film that is in close contact with the polarizer can be formed.

[0098] As the organic solvent, any suitable solvent capable of dissolving or uniformly dispersing the epoxy resin can be used. Specific examples of the solvent include ethyl acetate, toluene, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclopentanone, and cyclohexanone.

[0099] The solution may be applied to any suitable substrate or to a polarizer. When the solution is applied to a substrate, the solidified coating film formed on the substrate is transferred to the polarizer. When the solution is applied to a polarizer, the coating film is dried (solidified) to form a protective layer directly on the polarizer. Preferably, the solution is applied to a polarizer, and a protective layer is formed directly on the polarizer. With this configuration, the adhesive layer or pressure-sensitive adhesive layer required for transfer can be omitted, so that the polarizing plate can be made even thinner. The method of applying the solution is as described above.

[0100] By drying (solidifying) the coating film of the solution, a protective layer, which is a solidified coating film, can be formed. The drying temperature is preferably 100° C. or lower, and more preferably 50° C. to 70° C. If the drying temperature is within this range, adverse effects on the polarizer can be prevented. The drying time can vary depending on the drying temperature. The drying time can be, for example, 1 minute to 10 minutes.

[0101] B. Polarizing plate with retardation layer B-1. Overall structure of polarizing plate with retardation layer FIG. 7 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. The retardation layer-attached polarizing plate 200 in the illustrated example includes the polarizing plate 100 and the retardation layer 120 described in the above section A. Therefore, the retardation layer-attached polarizing plate 200 has the same irregular shape as the polarizing plate 100. In the retardation layer-attached polarizing plate 200, the retardation layer 120 can also function as a protective layer for the polarizer 10. The retardation layer 120 is typically laminated on the polarizing plate 100 (the polarizer 10 in the illustrated example) via an adhesive layer (not shown). The adhesive layer is an adhesive layer or a pressure-sensitive adhesive layer, and is preferably a pressure-sensitive adhesive layer (for example, an acrylic pressure-sensitive adhesive layer) from the viewpoint of reworkability and the like. Although not shown, the retardation layer-attached polarizing plate may have another protective layer (not shown) on the retardation layer 120 side of the polarizer 10, if necessary. If necessary, the retardation layer-attached polarizing plate may have another retardation layer (not shown) on the opposite side of the retardation layer 120 to the polarizing plate 100. The other retardation layer is typically a so-called positive C plate whose refractive index characteristics show the relationship nz>nx=ny.

[0102] The retardation layer 120 preferably has Re(550) of 100 nm to 190 nm, and Re(450) / Re(550) is preferably 0.8 or more and less than 1. Furthermore, the angle between the slow axis of the retardation layer 120 and the absorption axis of the polarizer 10 is preferably 40° to 50°.

[0103] B-2. Retardation layer The retardation layer 120 may have any appropriate optical characteristics and / or mechanical characteristics depending on the purpose. The retardation layer typically has a slow axis. In one embodiment, the angle θ between the slow axis of the retardation layer and the absorption axis of the polarizer 10 is preferably 40° to 50°, more preferably 42° to 48°, and further preferably about 45°, as described above. If the angle θ is in such a range, a retardation layer-attached polarizing plate having very excellent circular polarization characteristics (resulting in very excellent antireflection characteristics) can be obtained by using a λ / 4 plate as the retardation layer, as described later.

[0104] The retardation layer preferably exhibits a refractive index characteristic of nx > ny ≧ nz. The retardation layer is typically provided to impart antireflection properties to a polarizing plate and can function as a λ / 4 plate in one embodiment. In this case, the in-plane retardation Re(550) of the retardation layer is preferably 100 nm to 190 nm, more preferably 110 nm to 170 nm, and even more preferably 130 nm to 160 nm. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny < nz may occur.

[0105] The Nz coefficient of the retardation layer is preferably 0.9 to 3, more preferably 0.9 to 2.5, even more preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3. By satisfying such a relationship, when the polarizing plate with a retardation layer is used in an image display device, a very excellent reflected hue can be achieved.

[0106] The retardation layer may exhibit an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light, a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or a flat wavelength dispersion characteristic in which the retardation value hardly changes depending on the wavelength of the measurement light. In one embodiment, the retardation layer exhibits an inverse dispersion wavelength characteristic. In this case, Re(450) / Re(550) of the retardation layer is preferably 0.8 or more and less than 1, and more preferably 0.8 or more and 0.95 or less. With such a configuration, very excellent antireflection properties can be realized.

[0107] The absolute value of the photoelastic coefficient of the retardation layer is preferably 2 × 10 -11 m 2 / N or less, more preferably 2.0 × 10 -13 m 2 / N to 1.5 × 10 -11 m 2 / N, even more preferably 1.0 × 10 -12 m 2 / N to 1.2 × 10 -11 m 2If the absolute value of the photoelastic coefficient is within this range, the retardation is unlikely to change even when shrinkage stress occurs during heating. As a result, the thermal unevenness of the resulting image display device can be effectively prevented.

[0108] The retardation layer is typically made of a stretched resin film. In one embodiment, the thickness of the retardation layer is preferably 70 μm or less, more preferably 45 μm to 60 μm. If the thickness of the retardation layer is in such a range, curling during heating can be well suppressed and curling during lamination can be well adjusted. In addition, in an embodiment in which the retardation layer is made of a polycarbonate-based resin film as described below, the thickness of the retardation layer is preferably 40 μm or less, more preferably 10 μm to 40 μm, and further preferably 20 μm to 30 μm. By making the retardation layer of a polycarbonate-based resin film having such a thickness, it is possible to suppress curling and contribute to improving bending durability and reflection hue.

[0109] The retardation layer may be made of any suitable resin film that satisfies the above characteristics. Representative examples of such resins include polycarbonate-based resins, polyester carbonate-based resins, polyester-based resins, polyvinyl acetal-based resins, polyarylate-based resins, cyclic olefin-based resins, cellulose-based resins, polyvinyl alcohol-based resins, polyamide-based resins, polyimide-based resins, polyether-based resins, polystyrene-based resins, and acrylic-based resins. These resins may be used alone or in combination (for example, blended or copolymerized). When the retardation layer is made of a resin film that exhibits reverse dispersion wavelength characteristics, polycarbonate-based resins or polyester carbonate-based resins (hereinafter may be simply referred to as polycarbonate-based resins) may be suitably used.

[0110] As the polycarbonate-based resin, any suitable polycarbonate-based resin can be used as long as the effects of the present invention can be obtained. For example, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from at least one dihydroxy compound selected from the group consisting of an alicyclic diol, an alicyclic dimethanol, a di-, tri- or polyethylene glycol, and an alkylene glycol or a spiro glycol. Preferably, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, a structural unit derived from an alicyclic dimethanol, and / or a structural unit derived from a di-, tri- or polyethylene glycol; more preferably, it contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from a di-, tri- or polyethylene glycol. The polycarbonate-based resin may contain a structural unit derived from another dihydroxy compound as necessary. Details of polycarbonate-based resins that can be suitably used in the present invention are described, for example, in JP-A-2014-10291, JP-A-2014-26266, JP-A-2015-212816, JP-A-2015-212817, and JP-A-2015-212818, and these descriptions are incorporated herein by reference.

[0111] The glass transition temperature of the polycarbonate resin is preferably 110°C or higher and 150°C or lower, more preferably 120°C or higher and 140°C or lower. If the glass transition temperature is too low, the heat resistance tends to be poor, and dimensional changes may occur after film formation, and the image quality of the obtained organic EL panel may be reduced. If the glass transition temperature is too high, the forming stability during film formation may be poor, and the transparency of the film may be impaired. The glass transition temperature is determined in accordance with JIS K 7121 (1987).

[0112] The molecular weight of the polycarbonate resin can be expressed by reduced viscosity. The reduced viscosity is measured using methylene chloride as a solvent, a polycarbonate concentration precisely adjusted to 0.6 g / dL, and a temperature of 20.0°C ± 0.1°C using an Ubbelohde viscometer. The lower limit of the reduced viscosity is usually preferably 0.30 dL / g, more preferably 0.35 dL / g or more. The upper limit of the reduced viscosity is usually preferably 1.20 dL / g, more preferably 1.00 dL / g, and even more preferably 0.80 dL / g. If the reduced viscosity is smaller than the lower limit, the mechanical strength of the molded product may be reduced. On the other hand, if the reduced viscosity is larger than the upper limit, the flowability during molding may be reduced, and problems such as reduced productivity and moldability may occur.

[0113] A commercially available film may be used as the polycarbonate-based resin film. Specific examples of commercially available products include "Pure Ace WR-S", "Pure Ace WR-W", and "Pure Ace WR-M" manufactured by Teijin Limited, and "NRF" manufactured by Nitto Denko Corporation.

[0114] The retardation layer can be obtained, for example, by stretching a film formed from the polycarbonate-based resin. Any suitable molding method can be adopted as a method for forming a film from a polycarbonate-based resin. Specific examples include compression molding, transfer molding, injection molding, extrusion molding, blow molding, powder molding, FRP molding, cast coating (for example, casting), calendar molding, and heat pressing. The extrusion molding method or cast coating method is preferred. This is because it can increase the smoothness of the resulting film and obtain good optical uniformity. The molding conditions can be appropriately set according to the composition and type of the resin used, the properties desired for the retardation layer, and the like. As mentioned above, many film products of polycarbonate-based resins are commercially available, so the commercially available film may be directly subjected to the stretching treatment.

[0115] The thickness of the resin film (unstretched film) can be set to any appropriate value depending on the desired thickness of the retardation layer, the desired optical properties, the stretching conditions described below, etc. It is preferably 50 μm to 300 μm.

[0116] The stretching may be performed by any suitable stretching method and condition (e.g., stretching temperature, stretching ratio, stretching direction). Specifically, various stretching methods such as free end stretching, fixed end stretching, free end shrinkage, fixed end shrinkage, etc. may be used alone, simultaneously, or sequentially. Stretching may be performed in various directions or dimensions such as the length direction, width direction, thickness direction, and oblique direction. The stretching temperature is preferably Tg-30°C to Tg+60°C relative to the glass transition temperature (Tg) of the resin film, and more preferably Tg-10°C to Tg+50°C.

[0117] By appropriately selecting the above-mentioned stretching method and stretching conditions, a retardation film having the above-mentioned desired optical properties (for example, refractive index properties, in-plane retardation, Nz coefficient) can be obtained.

[0118] In one embodiment, the retardation film is produced by uniaxially stretching or fixed-end uniaxially stretching a resin film. A specific example of fixed-end uniaxial stretching is a method of stretching a resin film in the width direction (lateral direction) while running the resin film in the longitudinal direction. The stretching ratio is preferably 1.1 to 3.5 times.

[0119] In another embodiment, the retardation film can be produced by continuously obliquely stretching a long resin film in the direction of the above angle θ with respect to the longitudinal direction. By employing oblique stretching, a long stretched film having an orientation angle of angle θ with respect to the longitudinal direction of the film (slow axis in the direction of angle θ) can be obtained, and for example, roll-to-roll lamination with a polarizer is possible, and the manufacturing process can be simplified. The angle θ can be the angle formed by the absorption axis of the polarizer and the slow axis of the retardation layer in the retardation layer-attached polarizing plate. As described above, the angle θ is preferably 40° to 50°, more preferably 42° to 48°, and even more preferably about 45°.

[0120] An example of a stretching machine used for oblique stretching is a tenter type stretching machine capable of applying a feeding force, a pulling force, or a take-up force at different speeds in the transverse and / or longitudinal directions. Tenter type stretching machines include a transverse uniaxial stretching machine and a simultaneous biaxial stretching machine, and any appropriate stretching machine can be used as long as it can continuously obliquely stretch a long resin film.

[0121] By appropriately controlling the left and right speeds in the stretching machine, respectively, a retardation layer (essentially, a long retardation film) having the desired in-plane retardation and a slow axis in the desired direction can be obtained.

[0122] The stretching temperature of the film may vary depending on the in-plane retardation value and thickness desired for the retardation layer, the type of resin used, the thickness of the film used, the stretching ratio, etc. Specifically, the stretching temperature is preferably Tg-30°C to Tg+30°C, more preferably Tg-15°C to Tg+15°C, and most preferably Tg-10°C to Tg+10°C. By stretching at such a temperature, a retardation layer having suitable characteristics in the present invention can be obtained. Note that Tg is the glass transition temperature of the constituent material of the film.

[0123] C. Image display device The polarizing plate or the polarizing plate with a retardation layer can be applied to an image display device. Therefore, the embodiment of the present invention includes an image display device including such a polarizing plate or a polarizing plate with a retardation layer. Representative examples of the image display device include a liquid crystal display device and an electroluminescence (EL) display device (for example, an organic EL display device, an inorganic EL display device). The image display device according to the embodiment of the present invention includes the polarizing plate described in the above item A or the polarizing plate with a retardation layer described in the above item B on the viewing side. The polarizing plate with a retardation layer is laminated so that the retardation layer is on the image display cell (for example, a liquid crystal cell, an organic EL cell, an inorganic EL cell) side (so that the polarizer is on the viewing side). The image display device preferably has an irregular shape other than a rectangle. In such an image display device, the effect of the embodiment of the present invention is remarkable. Specific examples of the image display device having an irregular shape include an automobile meter panel, a smartphone, a tablet PC, and a smart watch. EXAMPLES

[0124] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows. In the examples and comparative examples, "parts" and "%" are by weight unless otherwise specified.

[0125] (1) Thickness The thickness was measured using an interference film thickness meter (Otsuka Electronics Co., Ltd., product name "MCPD-3000") The calculation wavelength range used for thickness calculation was 400 nm to 500 nm, and the refractive index was 1.53. (2) In-plane retardation of PVA (Re) For the polarizer (single polarizer) obtained by peeling and removing the resin substrate from the laminate of polarizer / thermoplastic resin substrate obtained in the examples and comparative examples, the in-plane retardation (Rpva) of PVA at a wavelength of 1000 nm was evaluated using a retardation measurement device (manufactured by Oji Scientific Instruments, product name "KOBRA-31X100 / IR") (this is the value obtained by subtracting the in-plane retardation (Ri) of iodine from the total in-plane retardation at a wavelength of 1000 nm according to the principle explained above). The absorption edge wavelength was set to 600 nm. (3) Birefringence of PVA (Δn) The birefringence (Δn) of the PVA was calculated by dividing the in-plane retardation of the PVA measured in (2) above by the thickness of the polarizer. (4) Single unit transmittance and polarization degree For the polarizer (single polarizer) obtained by peeling and removing the resin substrate from the laminate of polarizer / thermoplastic resin substrate obtained in the examples and comparative examples, the single transmittance Ts, parallel transmittance Tp, and crossed transmittance Tc were measured using an ultraviolet-visible spectrophotometer ("V-7100" manufactured by JASCO Corporation). These Ts, Tp, and Tc are Y values ​​measured using a 2-degree visual field (C light source) according to JIS Z 8701 and corrected for visibility. From the obtained Tp and Tc, the polarization degree P was calculated using the following formula. Polarization degree P(%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100 It should be noted that equivalent measurements can also be made using a spectrophotometer such as the Otsuka Electronics LPF-200, and it has been confirmed that equivalent measurement results can be obtained regardless of which spectrophotometer is used. (5) Puncture strength (breaking strength per unit thickness) The polarizer was peeled off from the laminate of polarizer / thermoplastic resin substrate obtained in the examples and comparative examples, and placed on a compression tester (manufactured by Kato Tech, product name "NDG5" needle penetration force measurement specifications) equipped with a needle, and pierced at a piercing speed of 0.33 cm / sec under a room temperature (23°C ± 3°C) environment. The strength at which the polarizer broke was taken as the breaking strength. The evaluation value was the average value of the breaking strengths measured for 10 sample pieces. The needle used had a tip diameter of 1 mmφ and 0.5R. The polarizer to be measured was fixed by clamping both sides of the polarizer with a jig having a circular opening with a diameter of about 11 mm, and the needle was pierced into the center of the opening to perform the test. (6) Orientation function of PVA For the polarizer (single polarizer) obtained by peeling off the resin substrate from the laminate of polarizer / thermoplastic resin substrate obtained in the examples and comparative examples, a Fourier transform infrared spectrophotometer (FT-IR) (manufactured by Perkin Elmer, product name: "Frontier") was used to measure attenuated total reflection (ATR) spectroscopy of the polarizer surface on the surface opposite to the surface on which the resin substrate was peeled off, using polarized infrared light as the measurement light. Germanium was used as the crystallite to which the polarizer was attached, and the angle of incidence of the measurement light was 45°. The orientation function was calculated by the following procedure. The polarized infrared light (measurement light) to be incident was polarized light (s-polarized light) that vibrated parallel to the surface to which the germanium crystal sample was attached, and the absorbance spectrum of each was measured with the stretching direction of the polarizer arranged perpendicular (⊥) and parallel ( / / ) to the polarization direction of the measurement light. From the obtained absorbance spectrum, (3330 cm -1 Intensity) was used as a reference (2941 cm -1 The intensity I was calculated. ⊥ is obtained from the absorbance spectrum obtained when the stretching direction of the polarizer is arranged perpendicular (⊥) to the polarization direction of the measurement light (2941 cm -1 strength) / (3330cm -1 In addition, I / / is obtained from the absorbance spectrum obtained when the stretching direction of the polarizer is arranged parallel ( / / ) to the polarization direction of the measurement light (2941 cm -1 strength) / (3330cm -1 Intensity), where (2941 cm -1 Intensity) is the bottom of the absorbance spectrum, 2770 cm -1 and 2990cm -1 2941cm when using this as the baseline -1 is the absorbance of (3330cm -1 Strength) is 2990cm -1 and 3650cm -1 3330cm when the baseline is -1 The absorbance of the obtained I ⊥ and I / / The orientation function f was calculated according to formula 1. Note that f = 1 is perfect orientation, and f = 0 is random. -1 The peak at 3330cm is said to be due to the vibration of the main chain (-CH2-) of PVA in the polarizer. -1 The peak is said to be due to the vibration of the hydroxyl group of PVA. (Formula 1)f=(3 <cos 2 θ>-1) / 2 =(1-D) / [c(2D+1)] however c = (3cos 2 β-1) / 2 So, as mentioned above, 2941cm -1 When using this function, β=90°⇒y=-2×(1-D) / (2D+1). θ: Angle of molecular chain to stretching direction β: Angle of the transition dipole moment with respect to the chain axis D=(I ⊥ ) / (I / / ) I ⊥ : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are perpendicular I / / : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are parallel (7) Crack occurrence rate A surface protective film was temporarily attached to the protective layer surface of the polarizing plate (or polarizing plate with retardation layer) obtained in the examples and comparative examples. Next, a separator was temporarily attached to the adhesive layer of the polarizing plate (or polarizing plate with retardation layer). This laminate was cut to about 130 mm x about 70 mm. At this time, it was cut so that the absorption axis of the polarizer was in the short direction. A U-shaped notch with a width of 5 mm, a depth (length of the recess) of 6.85 mm, and a curvature radius of 2.5 mm was formed in the center of the short side of the cut laminate. The U-shaped notch was formed by end mill processing. The outer diameter of the end mill was 4 mm, the feed rate was 500 mm / min, the rotation speed was 35000 rpm, and the cutting amount and the number of cutting times were 0.2 mm / time for rough cutting and 0.1 mm / time for finish cutting, a total of 2 times. The separator was peeled off from the laminate with the U-shaped notch formed, and attached to a glass plate (thickness 1.1 mm) via an acrylic adhesive layer. Finally, the surface protective film was peeled off to obtain a test sample having a structure of protective layer / polarizer / adhesive layer / glass plate (or protective layer / polarizer / adhesive layer / retardation layer / adhesive layer / glass plate). This test sample was subjected to a heat shock test in which the test sample was held at -40°C for 30 minutes and then held at 85°C for 30 minutes for 300 cycles, and the presence or absence of L-shaped cracks after the test was visually confirmed. This evaluation was performed using three polarizing plates (or polarizing plates with retardation layers), and the number of polarizing plates (or polarizing plates with retardation layers) in which cracks (effectively L-shaped cracks) occurred was evaluated.

[0126] [Example 1] 1. Preparation of Polarizer The thermoplastic resin substrate was a long, amorphous, isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) with a water absorption rate of 0.75% and a Tg of approximately 75°C. One side of the resin substrate was subjected to corona treatment (treatment conditions: 55 W min / m 2 ) was applied. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER Z410") in a ratio of 9:1. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched at its free end to 2.4 times its original size in the machine direction (longitudinal direction) between rolls with different peripheral speeds in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the final polarizer would be 40.5% (dyeing process). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration 4.0 wt %, potassium iodide 5.0 wt %) at a liquid temperature of 62°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds so that the total stretching ratio was 3.0 times (underwater stretching treatment: the stretching ratio in the underwater stretching treatment was 1.25 times). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, while drying in an oven maintained at 90°C, it was brought into contact with a SUS heated roll whose surface temperature was maintained at 75°C for about 2 seconds (drying shrinkage treatment). The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment was 2%. In this manner, a polarizer having a thickness of 7.4 μm was formed on the resin substrate.

[0127] 2. Preparation of Polarizing Plates 15 parts of an epoxy resin having a biphenyl skeleton (manufactured by Mitsubishi Chemical Corporation, product name: jER (registered trademark) YX4000) and 10 parts by weight of an oxetane resin (manufactured by Toagosei Co., Ltd., product name: Aron Oxetane (registered trademark) OXT-221) were dissolved in 73 parts of methyl ethyl ketone to obtain an epoxy resin solution. 2 parts of a photocationic polymerization initiator (manufactured by San-Apro Co., Ltd., product name: CPI (registered trademark)-100P) were added to the obtained epoxy resin solution to obtain a protective layer forming composition. The obtained protective layer forming composition was applied directly (i.e., without forming an easy-adhesion layer) to the polarizer surface of the resin substrate / polarizer laminate obtained in 1 above using a wire bar, and the applied film was dried at 60°C for 3 minutes. Next, a high-pressure mercury lamp was used to measure the accumulated light amount of 600 mJ / cm. 2 The film was irradiated with ultraviolet light so that the thickness of the protective layer was 3 μm. The resin substrate was then peeled off, and an acrylic adhesive layer (thickness 15 μm) was provided on the peeled surface. In this way, a polarizing plate having a configuration of protective layer (photocationically cured layer of epoxy resin) / polarizer / adhesive layer was obtained.

[0128] [Examples 2 to 4] A polarizer (thickness: 7.4 μm) was formed on a resin substrate in the same manner as in Example 1, except that a dye bath with a different iodine concentration (weight ratio of iodine to potassium iodide=1:7) was used. The following procedure was the same as in Example 1, and a polarizing plate having a configuration of protective layer (photocationically cured layer of epoxy resin) / polarizer / adhesive layer was obtained.

[0129] [Example 5] A polarizer (thickness: 6.7 μm) was formed on a resin substrate in the same manner as in Example 1, except that the stretching ratio in the underwater stretching was 1.46 times (as a result, the total stretching ratio was 3.5 times). The following procedure was the same as in Example 1, and a polarizing plate having a configuration of protective layer (photocationically cured layer of epoxy resin) / polarizer / adhesive layer was obtained.

[0130] [Example 6-1] A polarizer (thickness: 6.7 μm) was formed on a resin substrate in the same manner as in Example 5, except that a dye bath with a different iodine concentration (weight ratio of iodine to potassium iodide = 1:7) was used. The following procedure was the same as in Example 1, and a polarizing plate having a configuration of protective layer (photocationically cured layer of epoxy resin) / polarizer / adhesive layer was obtained.

[0131] [Example 6-2] A laminate of resin substrate / polarizer (thickness: 6.7 μm) was obtained in the same manner as in Example 6-1. On the other hand, 20 parts of epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name: jER (registered trademark) YX6954BH30, weight average molecular weight: 36000, epoxy equivalent: 13000) was dissolved in 80 parts of methyl ethyl ketone to obtain an epoxy resin solution (20%). This epoxy resin solution was applied to the polarizer surface of the laminate using a wire bar, and the coating film was dried at 60° C. for 3 minutes to form a protective layer constituted as a solidified coating film. The thickness of the protective layer was 3 μm. Next, the resin substrate was peeled off, and an acrylic adhesive layer similar to that of Example 1 was provided on the peeled surface. In this manner, a polarizing plate having a configuration of protective layer (solidified layer of coating film of epoxy resin) / polarizer / adhesive layer was obtained.

[0132] [Example 6-3] A laminate of resin substrate / polarizer (thickness: 6.7 μm) was obtained in the same manner as in Example 6-1. A polyurethane-based water-based dispersion resin (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name: Superflex SF210) was applied to the polarizer surface of the obtained laminate to a thickness of 0.1 μm as an easy-adhesion layer to form an easy-adhesion layer. Meanwhile, 20 parts by weight of an acrylic resin (manufactured by Kusumoto Chemicals Co., Ltd., product name: B-728) which is 100% polymethyl methacrylate was dissolved in 80 parts by weight of methyl ethyl ketone to obtain an acrylic resin solution (20%). This acrylic resin solution was applied to the surface of the easy-adhesion layer using a wire bar, and the coating film was dried at 60° C. for 5 minutes to form a protective layer constituted as a solidified product of the coating film. The thickness of the protective layer was 2 μm. Furthermore, a hard coat layer (thickness 3 μm) was further formed on the surface of the protective layer opposite to the easy-adhesion layer. The hard coat (HC) layer was prepared by mixing 70 parts by weight of dimethylol-tricyclodecane diacrylate (Kyoeisha Chemical Co., Ltd., product name: Light Acrylate DCP-A), 20 parts by weight of isobornyl acrylate (Kyoeisha Chemical Co., Ltd., product name: Light Acrylate IB-XA), 10 parts by weight of 1,9-nonanediol diacrylate (Kyoeisha Chemical Co., Ltd., product name: Light Acrylate 1.9NA-A), and 3 parts by weight of a photopolymerization initiator (BASF, product name: Irgacure 907) using an appropriate solvent, and applying the resulting coating liquid onto the protective layer surface so as to have a thickness of 3 μm after curing. The solvent was then dried, and the coating was applied to the protective layer using a high-pressure mercury lamp with an integrated light dose of 300 mJ / cm. 2 The film was formed by irradiating ultraviolet light under a nitrogen atmosphere so that the film thickness was 100 nm. Finally, the resin substrate was peeled off, and an acrylic adhesive layer similar to that in Example 1 was provided on the peeled surface. In this way, a polarizing plate having a structure of HC layer / protective layer (solidified layer of acrylic resin coating film) / easy adhesion layer / polarizer / adhesive layer was obtained.

[0133] [Examples 7 to 8] A polarizer (thickness: 6.7 μm) was formed on a resin substrate in the same manner as in Example 5, except that a dye bath with a different iodine concentration (weight ratio of iodine to potassium iodide = 1:7) was used. The following procedure was the same as in Example 1, and a polarizing plate having a configuration of protective layer (photocationically cured layer of epoxy resin) / polarizer / adhesive layer was obtained.

[0134] [Examples 9 to 12] A polarizer (thickness: 6.2 μm) was formed on a resin substrate in the same manner as in Example 1, except that the stretching ratio in the underwater stretching was 1.67 times (resulting in a total stretching ratio of 4.0 times) and a dye bath with a different iodine concentration (weight ratio of iodine to potassium iodide = 1:7) was used. The following procedure was the same as in Example 1, and a polarizing plate having a configuration of protective layer (photocationically cured layer of epoxy resin) / polarizer / adhesive layer was obtained.

[0135] [Examples 13 to 16] A polarizer (thickness: 6.0 μm) was formed on a resin substrate in the same manner as in Example 1, except that the stretching ratio in the underwater stretching was 1.88 times (resulting in a total stretching ratio of 4.5 times) and a dye bath with a different iodine concentration (weight ratio of iodine to potassium iodide = 1:7) was used. The following procedure was the same as in Example 1, and a polarizing plate having a configuration of protective layer (photocationically cured layer of epoxy resin) / polarizer / adhesive layer was obtained.

[0136] [Comparative Example 1] A polarizer (thickness: 5.5 μm) was formed on a resin substrate in the same manner as in Example 1, except that the stretching ratio in the underwater stretching was 2.29 times (as a result, the total stretching ratio was 5.5 times). The following procedure was the same as in Example 1, and a polarizing plate having a configuration of protective layer (photocationically cured layer of epoxy resin) / polarizer / adhesive layer was obtained.

[0137] [Comparative Example 2-1] A polarizer (thickness: 5.5 μm) was formed on a resin substrate in the same manner as in Comparative Example 1, except that a dye bath with a different iodine concentration (weight ratio of iodine to potassium iodide = 1:7) was used. The following procedure was the same as in Example 1, to obtain a polarizing plate having a configuration of protective layer (photocationically cured layer of epoxy resin) / polarizer / adhesive layer.

[0138] [Comparative Example 2-2] A polarizing plate having a structure of protective layer (solidified layer of epoxy resin coating film) / polarizer / adhesive layer was obtained in the same manner as in Comparative Example 2-1, except that a protective layer was formed using the same epoxy resin solution as in Example 6-2.

[0139] [Comparative Example 2-3] A polarizing plate having a configuration of protective layer (solidified layer of acrylic resin coating film) / polarizer / adhesive layer was obtained in the same manner as in Comparative Example 2-1, except that a protective layer was formed using the same acrylic resin solution as in Example 6-3.

[0140] [Comparative Examples 3 to 4] A polarizer (thickness: 5.5 μm) was formed on a resin substrate in the same manner as in Comparative Example 1, except that a dye bath with a different iodine concentration (weight ratio of iodine to potassium iodide = 1:7) was used. The following procedure was the same as in Example 1, to obtain a polarizing plate having a configuration of protective layer (photocationically cured layer of epoxy resin) / polarizer / adhesive layer.

[0141] [Example 17] 1. Preparation of retardation film that constitutes the retardation layer Polymerization was carried out using a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and a reflux condenser controlled at 100° C. Bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane 29.60 parts by mass (0.046 mol), isosorbide (ISB) 29.21 parts by mass (0.200 mol), spiroglycol (SPG) 42.28 parts by mass (0.139 mol), diphenyl carbonate (DPC) 63.77 parts by mass (0.298 mol), and calcium acetate monohydrate 1.19×10 as a catalyst. -2 Part of mass (6.78×10 -5mol) was charged. After the inside of the reactor was purged with nitrogen under reduced pressure, heating was performed with a heat medium, and stirring was started when the inside temperature reached 100 ° C. 40 minutes after the start of the temperature increase, the inside temperature was reached 220 ° C., and while controlling to maintain this temperature, the pressure was reduced and 90 minutes after reaching 220 ° C., the pressure was reduced to 13.3 kPa. Phenol vapor by-produced with the polymerization reaction was led to a reflux condenser at 100 ° C., a small amount of monomer components contained in the phenol vapor were returned to the reactor, and the uncondensed phenol vapor was led to a condenser at 45 ° C. and recovered. Nitrogen was introduced into the first reactor to restore the pressure to atmospheric pressure, and the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Next, the temperature increase and pressure reduction in the second reactor were started, and the inside temperature was set to 240 ° C. and the pressure to 0.2 kPa in 50 minutes. Thereafter, polymerization was allowed to proceed until the specified stirring power was reached. When the predetermined power was reached, nitrogen was introduced into the reactor to restore pressure, and the produced polyester carbonate resin was extruded into water and the strands were cut to obtain pellets.

[0142] The obtained polyester carbonate resin (pellets) was vacuum-dried at 80°C for 5 hours, and then a long resin film having a thickness of 130μm was produced using a film-forming device equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder setting temperature: 250°C), a T-die (width 200mm, setting temperature: 250°C), a chill roll (setting temperature: 120-130°C) and a winder. The obtained long resin film was stretched while adjusting so as to obtain a predetermined retardation, and a retardation film having a thickness of 48μm was obtained. The stretching conditions were a stretching temperature of 143°C and a stretching ratio of 2.8 times in the width direction. The Re(550) of the obtained retardation film was 141nm, Re(450) / Re(550) was 0.86, and the Nz coefficient was 1.12.

[0143] 2. Preparation of polarizing plate with retardation layer A laminate of resin substrate / polarizer (thickness: 6.7 μm) was obtained in the same manner as in Example 6-1. A protective layer (photocationically cured layer of epoxy resin) was formed on the polarizer surface of the laminate in the same manner as in Example 1. Next, the resin substrate was peeled off, and the retardation film (retardation layer) obtained above was attached to the peeled surface via an acrylic adhesive layer having a thickness of 5 μm. At that time, the retardation layer was attached so that the slow axis of the retardation layer and the absorption axis of the polarizer were at an angle of 45°. Finally, an acrylic adhesive layer similar to that in Example 1 was provided on the surface of the retardation layer. In this way, a retardation layer-attached polarizing plate having a configuration of protective layer (photocationically cured layer of epoxy resin) / polarizer / adhesive layer / retardation layer / adhesive layer was obtained.

[0144] [Comparative Example 5] A laminate of resin substrate / polarizer (thickness: 5.5 μm) was obtained in the same manner as in Comparative Example 2-1. A retardation layer-attached polarizing plate having a configuration of protective layer (photocationically cured layer of epoxy resin) / polarizer / adhesive layer / retardation layer / adhesive layer was obtained in the same manner as in Example 17, except that this laminate was used.

[0145] The polarizing plates or retardation layer-attached polarizing plates obtained in the Examples and Comparative Examples were subjected to the above evaluations (2) to (7). The results are shown in Table 1.

[0146] [Table 1]

[0147] As is clear from Table 1, the polarizing plates and the retardation layer-attached polarizing plates of the examples suppressed the occurrence of cracks in the irregularly processed portion (U-shaped notch portion).

[0148] 8 to 10 show the relationship between the single transmittance of the polarizer obtained in the examples and comparative examples and the Δn, in-plane retardation, or orientation function of PVA. As shown in Figs. 8 to 10, even if the birefringence, in-plane retardation, or orientation function are approximately the same (and as a result, the degree of orientation is approximately the same), when the single transmittance is high, cracks are likely to occur in the irregularly shaped portion. For example, in Fig. 8, when Δn is 35(×10 -3), when the single transmittance is greater than about 44.2%, it no longer satisfies formula (1), and as a result, cracks occur as in Comparative Example 4. Therefore, in order to effectively suppress the occurrence of cracks in the irregularly processed portion, it is important to adjust the single transmittance (and, as a result, the amount of adsorption of the dichroic material) in addition to the degree of orientation of the PVA-based resin. It is also clear that a polarizer that satisfies formula (1), formula (2) and / or formula (3) is one in which these adjustments have been suitably performed, and therefore it is possible to suitably suppress the occurrence of cracks in the irregularly processed portion. [Industrial Applicability]

[0149] The polarizing plate of the present invention is used in image display devices, and is particularly suitable for use in image display devices having irregular shapes, such as automobile meter panels, smartphones, tablet PCs, and smart watches.

Claims

1. A polarizing plate having a polarizer and a protective layer disposed on at least one side of the polarizer, The polarizing plate has an irregular shape other than a rectangle, The protective layer is made of a resin film having a thickness of 10 μm or less, The polarizer is composed of a polyvinyl alcohol-based resin film containing a dichroic material, The polarizer has a single transmittance of 40.0% or more and a degree of polarization of 99.0% or more; the protective layer is made of at least one selected from the group consisting of a solidified coating film of a solution of a thermoplastic (meth)acrylic resin in an organic solvent, a photocationically cured product of an epoxy resin, and a solidified coating film of a solution of an epoxy resin in an organic solvent, The piercing strength of the polarizer is 30 gf / μm or more, Here, the piercing strength of the polarizer is the strength at which the polarizer breaks when a needle having a tip diameter of 1 mmφ and a radius of 0.5 R is pierced into the polarizer at a speed of 0.33 cm / sec.

2. 2. The polarizing plate according to claim 1, which satisfies the following formula (1), where x% is the single transmittance of the polarizer and y is the birefringence of the polyvinyl alcohol-based resin at a wavelength of 1000 nm: y<-0.011x+0.525 (1).

3. 3. The polarizing plate according to claim 1 or 2, which satisfies the following formula (2), where the single transmittance of the polarizer is x % and the in-plane retardation of the polyvinyl alcohol-based resin film at a wavelength of 1000 nm is z nm: z<-60x+2875 (2).

4. 4. The polarizing plate according to claim 1, wherein the polarizing element has a single transmittance of x% and the polyvinyl alcohol-based resin has an orientation function of f, and the polarizing plate satisfies the following formula (3): f<-0.018x+1.11 (3) Here, the orientation function of the polyvinyl alcohol resin is a value determined by an ATR method using a Fourier transform infrared spectrophotometer and polarized light as measuring light.

5. The polarizing plate according to claim 1 , wherein the polarizer has a thickness of 10 μm or less.

6. The polarizing plate according to claim 1 , wherein the irregular shape is selected from the group consisting of a through hole, a V-shaped notch, a U-shaped notch, a recess that is rectangular in plan view, and a combination thereof.

7. The polarizing plate according to claim 6 , wherein the U-shaped notch has a radius of curvature of 5 mm or less.

8. A polarizing plate described in any one of claims 1 to 7, wherein the softening temperature of the resin film is 100°C or higher.

9. 9. The polarizing plate according to claim 1, wherein the thermoplastic (meth)acrylic resin has at least one unit selected from the group consisting of a lactone ring unit, a glutaric anhydride unit, a glutarimide unit, a maleic anhydride unit, and a maleimide unit.

10. A polarizing plate according to any one of claims 1 to 9 and a retardation layer, The retardation layer is disposed on the side of the polarizer opposite to the side on which the protective layer is disposed.

11. The retardation layer has an Re(550) of 100 nm to 190 nm, and an Re(450) / Re(550) ratio of 0.8 or more and less than 1; 11. The polarizing plate with a retardation layer according to claim 10, wherein the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is 40° to 50°.

12. The polarizing plate with a retardation layer according to claim 10 , wherein the retardation layer is laminated on the polarizing plate via a pressure-sensitive adhesive layer.

13. An image display device comprising the polarizing plate according to claim 1 or the retardation layer-attached polarizing plate according to claim 10.

Citation Information

Patent Citations

  • Assembling of shield drilling machine

    JP1983011296A

  • Polarizing plate and method for manufacturing the same

    JP2001343521A

  • Polarizing film and polarizing plate including the same

    JP2017003954A

  • Polarizing plate, method for producing polarizing film, and method for producing polarizing plate

    JP2017182017A

  • Manufacturing methods for stretched film and polarizing film

    JP2017187731A